The role of ADR and judicial agreements: legal analysis and behavioral economics insights - Solano Mantilla, Valeria (LUISS Guido Carli, 2025)
From rationality to reality. The evolution of law and economics through the behavioral lens. Understanding how we choose: foundations of behavioral economics. Rethinking law through the lens of behavioral economics. Why law needs behavioral economics. The challenge of integrating behavioral economics into private law: freedom vs regulation. The double-edged sword of behavioral economics: protecting consumers from psychological manipulation. Balancing innovation and consumer rights: a global view on consumer protection in the EU, Italy and Colombia. Alternative dispute resolution and the judicial agreements. The justice system seen though behavioral economics. Judicial agreements: procedural autonomy and enhancing judicial cooperation. Alternative dispute resolution (ADR) and mediation: legal frameworks, party autonomy and behavioral economic. A brief comparative analysis on mediation: EU, Italy and Colombia. Applying behavioral economics in the ADR (mediation).
Keywords: ADR; Alternative dispute resolution; Economic behaviour; Mediation; Médiation

The regulation of crypto-assets in South Africa with particular regard to crypto-asset market manipulation - Mgijima, Lwandiso (University of Pretoria, 2025)
Market manipulation is one of the dishonest means used by unscrupulous investors to make unjustified profits. It is conduct which unlawfully interferes with the normal operations of the markets in order to create false appearances with respect to the trading activity or the price of a financial asset. Market abuse is one of the various challenges plaguing the crypto-assets market, and is one of the financial regulators’ priority concerns. This study examines and discusses the problem of market manipulation in crypto-assets, and the need for the enactment of an effective regulatory framework in order to combat this problem and to promote investor protection and safeguard the integrity of the markets. The study finds that South Africa and other countries need to introduce rules in crypto-assets market which aim at regulating the activities of crypto-asset service providers. Currently South Africa has not enacted a comprehensive regulatory framework to address the various illegal uses of crypto-assets. The general approach adopted by South Africa to regulate crypto-assets activities involves subjecting crypto-asset service providers and their activities under the various financial sector laws established to regulate the traditional financial markets. This approach has been criticised as being inefficient in light of the unique risks presented by crypto-assets. The study discusses some of these arguments in detail and concludes by highlighting the need for the adoption of innovative regulations, in the long term, which comprehensively and effectively addressed the various risks presented by crypto-assets which also include market manipulation.
Keywords: Crypto-asset; Crypto-assets; Framework; Manipulation; Markets; Misconduct; Regulation; Service provider

Climate justice and litigation in the context of South Africa - Chihombe, Denmark (North-West University, 2025)
This study interrogates the intersection of climate justice and litigation in the South African context. It addresses the urgent need for legal methods to address the disproportionate impact of climate change on marginalised communities. As climate change has become one of the greatest global challenges, marginalised communities most keenly feel its impacts, particularly those historically disadvantaged by socioeconomic inequalities rooted in apartheid. What follows is a critical examination of the most important international climate frameworks, in particular the United Nations Framework Convention on Climate Change (hereinafter UNFCCC) and the Paris Agreement, which have shaped the global discourse on climate change. The increasing recognition of the rights of historically marginalised and vulnerable communities underscores the potential role of climate litigation in achieving climate justice for all by holding both government and corporations accountable for their actions and lack thereof in mitigating climate change. The study examines the South African legal framework and recognises its progressive constitution that guarantees environmental rights. On the other hand, the study highlights significant barriers to effective climate action, particularly for the country’s most vulnerable, poor and marginalised populations, who often lack access to legal resources and skills needed for climate action. Using decided climate cases such as Earthlife Africa v. Minister of Environment, the study highlights the problems that plaintiffs often face when it comes to proving causation and the need for expert evidence in such litigation. Finally, the study concludes that while climate litigation offer opportunities for climate justice, the challenges identified need to be addressed to ensure the effectiveness of climate processes in achieving climate justice. The study therefore makes recommendations for strengthening legal aid, promoting public climate litigation and improving community capacity. By implementing these recommendations, climate justice will be achieved so that South Africa can effectively utilise climate litigation to demand climate justice for both current and future generations.
Keywords: Climate change; Global challenges; Justice; Litigation; Marginalised communities

A legal analysis of the application of the FATF grey-listing standards on South Africa - Mthembu, Zanele (North-West University, 2025)
The Financial Action Task Force (FATF) is a watchdog established to counter the abuse of the financial system by criminals for money laundering, the financing acts of terrorists and proliferation financing. For the FATF to achieve its mandate, it came up with a set of global standards in the form of Recommendations. The Recommendations seek to mitigate the risks of money laundering and terrorist financing and to assess whether FATF member countries are taking effective action to combat money laundering and terrorist financing. South Africa is a member of the FATF and therefore, is obliged to comply with the standards set to combat money laundering and terrorist financing and proliferation. The FATF uses assessments done through peer mutual evaluations. In other words, FATF members assess one another’s anti-money laundering and counter-terrorism financing (AML/CTF) regulatory frameworks for compliance with FATF’s standards. Following the FATF's assessment in the years 2003, 2009 and 2018, South Africa’s AML/CTF regulatory framework was found to be weak leading to greylisting in 2023. The greylisting of South Africa follows the findings of strategic deficiencies in the country’s implementation of the FATF AML/CFT standards. Greylisting by the FATF carries various economic and reputational implications for South Africa such as increased scrutiny from international partners resulting in increased compliance costs for financial institutions, an estimated reduction in South Africa’s gross domestic product (GDP) and a decrease in foreign direct investment (FDI). Since the greylisting, South Africa has embarked on a legislative and regulatory journey to address the shortcomings with a view to be taken off the greylist. This dissertation provides a detailed analysis of the FATF standards, evaluates South Africa's legislative and institutional responses in the form of the Prevention of Organised Crime Act 121 of 1998, Financial Intelligence Centre Act 38 of 2001 and the Protection of Constitutional Democracy Against Terrorist and Related Activities Act 33 of 2004, and assess their effectiveness in addressing the identified deficiencies. Recommendations are suggested to assist in fortifying South Africa’s AML/CTF regulatory framework.
Keywords: Accountable institutions; GAFI; Greylist; Money laundering; Mutual evaluation; Recommendations; Terrorism financing

The interpretation of social relations in the environmental, social and governance framework - Nxumalo, Nyiko (North-West University, 2025)
Environmental, social and governance (ESG) issues have gained prominence in recent years. Companies have come to understand their role in the global economy and that their decisions cannot be based solely on profits. They are now required to have regard for the environment in which they operate, to be mindful of the social factors that affect their employees, customers and the community at large, and to ensure that their corporate governance complies with the standards set out in the Companies Act 71 of 2008 and the various King Reports. While ESG has become a buzz word in the corporate world, there is still much uncertainty among stakeholders about what they are required to do and what the reporting requirements, if any, are. Its implementation in South Africa is still in its infancy and there is much uncertainty about what ESG monitoring and compliance truly entail. A perfect illustration of this is the fact that the Johannesburg Stock Exchange (JSE) only published ESG disclosure guidelines for the first time in 2022. This means that until the guidelines were published, hundreds of companies in South Africa had been wondering aimlessly in the dark when it comes to ESG issues. To make matters worse, while environmental issues and corporate governance issues have received significant attention from scholars and legislators in South Africa alike, the "S" in ESG has received little attention. It is often treated as the undesirable stepchild that everyone conveniently forgets is part of the ESG family. The purpose of this study is to highlight the gaps in the existing ESG regulatory framework, which leads to gaps in the understanding and monitoring of the implementation of the social indicators of ESG. The study aims to firstly determine whether companies in South Africa have a proper understanding of the social framework of ESG and whether the current legal and/or regulatory framework in South Africa offers sufficient guidance to n organisations to ensure that they comply with and fully implement the social guidelines of the ESG framework.
Keywords: ESG; ESG Framework; Governance factors; King IV report; Section 29 of Companies Act; Social factors; Social indicators

Expedited procedures in the Multilateral Investment Court: efficiency and consistency - Shouzab, Ali (Uppsala universitet, 2025)
The ongoing ISDS reform, under UNCITRAL Working Group III with a substantial input from the EU, has recently proposed for the establishment of a Multilateral Investment Court (MIC) with an appellate mechanism. Simultaneously, expedited arbitration procedures have gathered significant academic interest in the recent decades. While extensive literature exists on both the MIC development and expedited procedures, their intersection remains relatively unexplored. This dissertation bridges this research gap by analyzing how the best practices from different expedited procedures and EU treaties could be used to establish expedited MIC procedures. Adopting a doctrinal methodology, the research identifies the prominent models and trends in different expedited procedures, accesses their compatibility with the objectives of MIC, and finally proposes a suitable model to attain (cost and time) efficiency and consistency both for the first-tier and appellate proceedings in MIC. By doing so, the study contributes some recommendations for the development of expedited MIC procedures.
Keywords: Appellate Proceedings; Consistency; Efficiency; Expedited MIC Procedures; Expedited Procedures; First-Tier Proceedings; ISDS Reform; Multilateral Investment Court (MIC); UNCITRAL Working Group III

Perspectives of post-commencement financiers regarding their voting rights on a business rescue plan - Van Niekerk, Larisa (University of Pretoria, 2024)
Post-commencement financiers provide a lifeline to companies under business rescue and these financiers have their best interest in the survival of these companies. Should it be that the business rescue plan is unsuccessful, the chances are that the post commencement financiers will be the largest creditors. In Wescoal Mining (Pty) Ltd v Mkhombo NO, a dispute arose regarding the appropriate adoption of a business rescue plan during the meeting. One critical legal issue was whether the Companies Act bestows voting rights exclusively to the company's creditors who existed at the initiation of business rescue, or if creditors accruing after the commencement may also partake in voting on the plan. Following an assessment by Judge Wilson, it was established that only creditors with claims predating the commencement were eligible to participate in the voting process. Subsequently, Judge Wilson believed that section 135 of the Companies Act places post-commencement financiers as creditors in a different class and provides for their protection and interests in a different way. Against this background, the dissertation evaluates the position of post-commencement creditors when it comes to voting on a business rescue plan.
Keywords: Business rescue; Company law; Creditors; Insolvency; Insolvency law; Life-line; Post-commencement creditors; Post-commencement finance

Climate change and international investment law : lessons from Africa's investment treaty practice - Mogashoa, Lebogang Paul (University of Pretoria, 2024)
This dissertation critically analyses new generation continental, regional and bilateral investment treaties in Africa with the aim to explore enhancements that could be made thereto in order to enable African citizens to hold investors accountable for investment-related climate change issues in Africa. The main research question answered in the dissertation is: to what extent does African investment treaty practice incorporate climate change-related provisions and investor accountability for climate change. The dissertation analysed traditional investment treaties, particularly noting their silence on climate change and investor accountability, and their partiality to investor protection. Using the AfCFTA Investment Protocol as an anchor alongside other new generation continental, regional and bilateral investment treaties in Africa, it discusses a fundamental contemporary shift in African investment treaty practice towards ensuring sustainable investments and greater investor accountability for sustainability in Africa. It also explores the various limitations in these new generation investment treaties that still make investor accountability. In the end it proposes reforms to the Investor-State Dispute Settlement provisions of these investment treaties to recognise citizen-led arbitral claims against investors, utilising the Hague Rules on Business and Human Rights as the procedural infrastructure for handling arbitration of such claims.
Keywords: AfCFTA; African Continental Free Trade Area; Climate change; ISDS; Investment treaties; Investments; Investor-State Dispute Settlement

The relationship between the business rescue practitioner and the directors of the company - Mokoka, Neo (University of Pretoria, 2024)
This dissertation on the relationship between the business rescue practitioner and the directors of the company under business rescue. In essence, this dissertation investigates whether a conflict arises between the duties, roles and powers of the business rescue practitioner and those of directors of the financially distressed company. The aim of this dissertation is to study what are the limitation on duties, roles and powers of directors of the company as a result of the appointment of the business rescue practitioner and the extent thereof. In achieving the above objective, this dissertation commences with setting out the background of business rescue proceedings in South Africa by analysing provisions of Chapter 6 of the Companies Act 71 of 2008 which has introduced “a new corporate rescue procedure” in South Africa, being business rescue. The focus is on provisions dealing with duties, roles and powers of directors in the ordinary course as set out in section 66, 75 to 77 of the Act. The focus then shifts to the provisions dealing with the commencement of business rescue proceedings, the appointment of the business rescue practitioner and his duties, roles and powers. In order to establish whether a conflict truly exists between the duties, roles and powers, various sources dealing with this issue are considered. In order to assess whether there are solutions in dealing with the conflict and/or limitation that arises, this dissertation includes a comparative study on selected foreign jurisdictions dealing with the interaction between the board of directors and business rescue practitioner are considered. In particular, this dissertation considers corporate rescue mechanisms in the Commonwealth of Australia, the United Kingdom and the United States of America. The purpose of the comparative study is to determine which lessons can be learned from the practices in the aforementioned jurisdictions. The overall objective of this study is to determine how the South African legal framework pertaining to the interaction between directors and business rescue practitioners can be enhanced.
Keywords: Business rescue; Business rescue practitioner; Companies Act 71 of 2008; Comparative study; Duties of directors; Limitations on powers; Powers of directors; Roles of directors; US bankruptcy code

Theories on the nature and purpose of the company and their implications for corporate governance - Ramalho, Anna Francina (University of Pretoria, 2024)
Despite the emergence of corporate governance as a formal discipline more than thirty years ago, the proliferation internationally of scholarly work on the topic and its formal regulation over this period, the scope, definition and direction of corporate governance remain contested. Company theories could potentially assist in this regard but have been inconsistent in their explanations of the both the means and ends of corporate governance. This has led to scepticism about the efficacy of theories to illuminate the phenomena associated with companies and company law. Notwithstanding, theory is critical as it makes explicit what is implicit in policymaking by regulators, as well as in the behaviour and decision-making by corporate actors, so that regulation and decisions are transparent for analysis and evaluation. The study, therefore, set out to provide a synthesis and doctrinal analysis of the main theories on the nature and general purpose of corporations in historical context. It was found that objections can be raised against all of these theories to a greater or lesser extent for inaccurate portrayal of the law, limited explanatory power and detachment from the real word. This study shows that corporate theories are a product of the settings in which they have developed and consequently none of these theories represents a universal or absolute truth, nor are they an inevitability due to widespread adoption and use. This leaves room for new formulations of the corporate form and its purpose fit for today’s context with its political, social and environmental challenges. This dissertation also includes further directions for theoretical exploration.
Keywords: Contractarianism; Corporate governance; Entity theories; Shareholder primacy; Stakeholder theories

Selected problem areas pertaining to the removal of directors from office - Shange, Thandokuhle Wandile (University of Pretoria, 2024)
This paper constitutes a composite analysis of the legal framework and procedures for removing directors and the key challenges presented by the framework. It achieves this by looking at four legal questions: Firstly, it looks into what is the legal framework for director removal in South Africa, secondly, it delves into the challenges and/or uncertainties presented by this process, and further explores if there are any possible learnings South Africa can learn from foreign jurisdiction.
Keywords: Companies Act 2008; Comparative company law; Director removal; Director’s right; Judicial review; Section 71

Proposed legal reforms to protect South Africa's informal social security - Zeelie, Robin Erin (University of Pretoria, 2024)
Informal social security is a non-governmental form of social security between kin and/or community members and is a prevalent practice in South Africa. The question this dissertation analyses is whether the South African government fails in its constitutional duty to protect and advance informal social security. The dissertation limits itself to analysing cash transfers through social grants, and social insurance in the Unemployment Insurance Act and the Compensation for Occupational Injuries and Diseases Act. This dissertation delineates its definition of informal social security, historically contextualises its practice, and explains the contemporary formal social security framework. This dissertation finds five prominent shortcomings in the formal framework, and that these shortcomings have a profoundly negative, weakening effect on informal social security, as the more people who rely on informal mechanisms, the less it can respond to needs arising from life contingencies, shocks, and risks. The dissertation concludes by analysing three legal reform proposals the state can implement: extending existing social insurance frameworks to those in the informal sector, promoting cooperatives as a formal platform for the informal, and the basic income grant.
Keywords: Basic income grant; Cooperatives; Duty; History; Informal social security; Republic of South Africa; Social assistance; Social security

'Banking' on artificial intelligence to enhance bank risk management - Chiba, Mayuree (University of Pretoria, 2024)
This dissertation investigates the impact of digital transformation on risk management within the banking sector, emphasizing the integration of artificial intelligence (AI) in enhancing operational risk management. It examines key research questions about how digitisation reshapes risk management practices, the extent to which South African banks align with international standards, and the role of AI in advancing these frameworks. The study finds that AI holds substantial potential to improve risk management, particularly in managing operational risks, while underscoring the indispensable role of human oversight. Ultimately, this shift toward a more AI-driven, adaptive approach marks a pivotal evolution in the financial sector, suggesting that the future of risk management can indeed rely on AI's transformative capabilities.
Keywords: Artificial Intelligence; Bank; Inteligência artificial; Intelligence Artificielle; Operational risk; Risk management

Facilitating Trade through Rules of Origin: A Consideration of the African Continental Free Trade Area - Okoroma, Blessing Ijeoma (University of Calgary, 2024)
Rules of origin play a pivotal role in free trade agreements. Apart from serving as a tool to distinguish goods by determining the nationality of a product, rules of origin have the capacity to increase trade relations or deter it. Of course, it is the hope of any viable state to increase profitable trading relations, and if rules of origin can help with that, it becomes expedient to fully understand how these rules of origin operate. In Africa, we see rules of origin being implemented amongst the Regional Economic Communities (RECs), but this has come with many struggles. In fact, low intra-African trade can be narrowed down to complex rules of origin regimes deployed in regional agreements in Africa. As of date, the major RECs have each implemented different rules of origin, leading to the co-existence of conflicting rules of origin across Africa. This non-uniformity in the rules of origin regimes in Africa has resulted in low continental trade in Africa. As such, these RECs have not yielded the expected increase in intra-African trade. With the creation of the African Continental Free Trade Area (AfCFTA), which currently doubles as the latest and largest FTA in Africa, it is expected that better rules of origin will be deployed to mitigate the existing intra-African trade deficits. This thesis thus deploys a doctrinal approach in determining whether AfCFTA’s rules of origin are positioned to achieve greater intra-African trade. Consequently, this thesis uncovers some lapses in AfCFTA’s rules of origin and calls for harmonization of all the rules of origin in Africa and recommends a possible amendment to Article 19 of the Agreement establishing AfCFTA to accommodate the intended harmonization.
Keywords: African Continental Free Trade Area; Free Trade Area; Rules of Origin

Taxpayer Confidentiality : implications of the tax secrecy provisions regarding illegal miners - Kgobe, Kgothatso (University of Pretoria, 2024)
Taxpayer confidentiality and its implications (if any), on illegal miners

Lessons for insolvency law from the emoluments attachment order experience - Grobler, Frederik (University of Pretoria, 2024)
Section 23(5) of the Insolvency Act poses an interesting challenge, namely vesting a portion of an insolvent’s post-sequestration income in the trustee of the insolvent estate without infringing on the insolvent’s constitutional rights. The income earned by the insolvent during sequestration is in general excluded from his estate and does not vest in the trustee, unless the Master determines that a portion of the insolvent’s income will not be required to maintain the insolvent and his dependents. In such a case, only the portion deemed to be surplus to requirements will be included in the insolvent estate and will vest in the trustee. The question of what role the insolvent’s income should play during the sequestration process, and therefore how section 23(5) should be interpreted and applied, has vexed the courts and numerous practical and constitutional issues arise. This study examines the application and shortcomings of section 23(5) during the administration phase of the sequestration process. It then explores the lessons learned during the recent constitutional scrutiny and subsequent amendment of the emoluments attachment process. Lastly, recommendations are made for possible law reform of section 23(5).

The development of explicit deposit insurance schemes in selected countries in Southern Africa - Moloi, Mbakiso Ndumiso (University of Pretoria, 2024)
This dissertation explores the evolution of explicit deposit insurance schemes (EDIS) in Southern African countries. It emphasises the important role of banks in the economy and their vulnerability to failures despite prudential requirements and supervision. Financial safety nets are essential for failing banks, and deposit insurance is the primary mechanism to protect depositors and maintain financial system stability in the event of a bank's failure. Originating in 1933 with the establishment of the Federal Deposit Insurance Corporation in the United States of America during the Great Depression, EDIS has become a global standard. Southern Africa, with its developing financial sector, faces many challenges including bank failures, causing depositors to lose funds. The region's high interconnectedness increases the threat of contagion if parent banks fail. The absence of deposit insurance raises the likelihood of fiscal authorities succumbing to political pressure to bailout failing banks during crises as seen during the 2007-09 Global Financial Crisis (GFC). The GFC prompted the International Association of Deposit Insurers and the Basel Committee on Banking Supervision to establish the Core Principles for Effective Deposit Insurance Systems. Issued in June 2009, these principles are used by jurisdictions as a benchmark for assessing the quality of their deposit insurance systems and identifying gaps in their deposit insurance practices. This research aims to evaluate international best practice standards for EDIS and extract lessons from the establishment of EDIS in the USA to address gaps in the implementation of deposit insurance schemes in Southern African countries. Examining ten Southern African countries, this research investigates varied progress in EDIS adoption. Case studies, particularly Zimbabwe as a pioneer of EDIS in the region and Namibia as a recent entrant, help to identify gaps and opportunities for enhancing deposit insurance frameworks in the region.

Rethinking Environmental Obligations in Corporate Insolvencies: What New Role for Lenders? - Ebegbodi, Daniel Onyeje (University of Calgary, 2024)
Environmental reclamation obligations are statutory mechanisms designed to regulate environmental protection by corporate entities. Bankruptcy laws on the other hand are meant to offer insolvent corporations an opportunity to reorganize their affairs, satisfy creditors claims and make a fresh start. In practice, the application of bankruptcy laws can undermine key environmental reclamation objectives, leading many to ask whether a corporation undergoing restructuring with significant outstanding environmental reclamation obligations should be able to commence bankruptcy proceedings to satisfy creditors’ claims? By employing the doctrinal and comparative research methodologies, this research interrogates that inquiry. It argues that, despite the importance of bankruptcy protection for corporations undergoing financial distress, environmental protection should be paramount. Although sustainable finance (SF) instruments have been deployed by banks to enable creditors to mitigate environmental concerns in their investments, the persistent recurrence of environmental reclamation issues in the oil and gas sector particularly during insolvencies, underscores the need for financial investors to strengthen their investment policies to reflect best practices providing the desired protection for the environment. The research finds that, although SF and environmental, social and governance (ESG) approaches, are commendable, they are insufficient in instilling adequate regulatory impact on the environment compared to judicial control offered by the courts. The thesis concludes that whilst judicial control mechanism is not without concerns, with government’s deliberate financial policy and judicial control to complement SF and ESG efforts, ESG and SF mechanisms can be strengthened to compel greater significant influence on best practices in lending.

Aspects of substantial compliance and strict compliance as applied to demand guarantees - Sikobi, Nkanyiso (University of South Africa, 2024)
Demand guarantees are essential for purposes of commerce and are used to secure the performance of the contractor. South African courts have held that demand guarantees are akin to letters of credit. Despite the independent nature of demand guarantees to the underlying contract, in circumstances where the beneficiary has made a fraudulent claim, the guarantor may dishonour the demand or claim. South African courts have indicated that if the underlying contract is illegal, courts may intervene by granting an interdict to stop payment under the guarantee. The South African law recognises traditional guarantees (often called suretyship) where the beneficiary, when making a demand or claim, must demonstrate liability on the part of the contractor. There are instances where courts have held that guarantees were of a nature akin to suretyship. In South Africa, parties entering into a demand guarantee contract are subject to the common law of contract. The Uniform Rules for Demand Guarantees, adopted by the International Chamber of Commerce, are only applied by explicit reference in the demand guarantee failing which such rules do not apply. Non-implementation of these rules has resulted in rigorous litigation in the recent years on this subject-matter. A demand must be supported by documents and require strict conformity. However, strict compliance with the prerequisites of the demand guarantee has not been applied consistently in South Africa. South African courts have recently been applying substantial compliance, in certain circumstances finding that a term in a guarantee is just directory and not obligatory. Furthermore, on many occasions, courts have deviated from strict compliance holding that a term in a guarantee does not make commercial sense thus such term is not mandatory. In this way, courts apply the most business-sensible interpretation when interpreting demand guarantees.
Keywords: Autonomous; Beneficiary; Contractor; Demand guarantees; Demand or conditional guarantee; Documentary letters of credit; Employer; First written demand; Fraud and illegality exception; Guarantor; Independence; Performance guarantees; Security for performance; Strict compliance; Substantial compliance; Suretyship; Underlying contract; Uniform rules for demand guarantees

The legal framework regulating the duties of insurance intermediaries - Sithole, Eugine (University of Pretoria, 2024)
In South Africa, before the Financial Advisory and Intermediaries Services Act (FAIS Act) and other insurance laws came into existence, intermediary services regarding the rendering of insurance products have always been regulated by the law of agency and mandate. This means that the Roman-Dutch principles provided for the standards to which the conduct of intermediaries was to comply with when rendering insurance services. The mandate of intermediaries in terms of the Roman-Dutch Principles also included the fact that they had to act with care, skill and in good faith. When the FAIS Act came into operation, it introduced several detailed rules and minimum standards for insurance intermediaries to comply with, and these minimum standards are not limited to qualifications, experiences and characteristics of honesty and integrity that an intermediary must comply with, but they also stipulated in detail what an intermediary must do when discharging insurance intermediary duties. The FAIS Act is the leading legislation when it comes to the regulation of intermediary services. The FAIS Act, under section 16, provides for a General Code of Conduct for Authorised Financial Services Providers and their Representative (GCC), which contains a set of rules that are applicable to all intermediaries. These rules under the GCC are aimed at ensuring that insurance customers are provided with material facts that will enable them to make a prior informed decision and that their reasonable financial needs concerning insurance products will be carefully considered so that they can be provided with a product that will be suitable to satisfy their needs. Furthermore, in terms of South African laws and practices, intermediaries play an essential role in the creation of legally binding insurance contracts. Insurance businesses are concluded through intermediaries. Considering that many insurance companies are juristic persons, and they can only conduct business by means of human agents, insurance laws make it compulsory for intermediaries to have skills, knowledge, and experience regarding insurance products that they are rendering to insurance customers. It is commonly believed that intermediaries with skills, knowledge and experience, they always act in the best interest of the client, and they ask relevant questions to assist the clients to disclose all material facts, and they always make sure that material facts are clearly communicated/disclosed to the insurer and insured to avoid future conflicts. The legal framework placed a duty on the intermediary to assist the insured to disclose all material facts and to explain all clauses contained in the insurance contract which may lead to the insurer repudiate its liability. Furthermore, an intermediary is at all material times expected to first consider the financial situation of the potential insured before determines a cover that will be best suitable for the insured’s needs. However, despite the best guidelines outlined by applicable insurance laws and regulations, mistakes are still being made by intermediaries, which lead to insurance customers to suffer the consequences of impractical intermediary services, and that has resulted in numerous complaints, legal disputes, debarments, and other regulatory actions. As a result of intermediaries’ continuous misconduct, insurers have been repudiating claims, and it has created a presumption that insurers conduct businesses to enrich themselves instead of protecting the interests of their customers as required by regulating legal framework. Therefore, so many people have lost confidence in the insurance industry due to unlimited court cases and complaints arising from misconduct or omissions of intermediaries, such as their failure to disclose material facts to the parties. Once it is found that material facts were not fully disclosed between the insurer and insured, both parties would have been deprived of their right to make an informed decision before consenting or signing a legally binding contract. Therefore, a need is created for intermediaries to be educated of their legal duties when rendering insurance services and that will help strengthen or restore the confidence of the public towards insurance industry.

The duty of bank confidentiality and the safeguarding of financial privacy - Ahmed, Kousar Bibi (University of KwaZulu-Natal, 2024)
Abstract available in PDF.
Keywords: Banks and privacy; Customer confidentiality; Duty of confidentiality; Protection of personal information

Corporate mergers: a comparative analysis of the Italian and American legal systems - Carboni, Ludovica (LUISS Guido Carli, 2024)
Mergers in the Italian and European legal system. The Italian legal landscape for mergers. Applicable regulations. Stages of the merger process. The first phase: the merger plan. The second phase: the merger resolution. The third phase: the merger deed. The protection of creditors. The invalidity of the merger. The FIAT-Chrysler merger. Evolution of the legal nature of mergers in the Italian legal system: legislative and jurisprudential perspectives. The extinguishing-successory orientation. The evolutionary–modifying orientation. Court of cassation ruling no. 2637 of 2006. Return to the extinguishing-successory orientation: judgement no. 21970/2021. Debate surrounding judgement 21970/2021: criticism and support. Mergers in the American legal system. The American legal landscape for mergers. The evolution of the US corporate law of mergers. Sources of corporate law. The merger process. Economic motives for mergers. Steps of the merger procedure. The merger plan. Merger between parent and subsidiary or between subsidiaries. Articles of merger. Effects of merger. Abandonment of a merger or share exchange. The ExxonMobil merger. Comparative analysis of the Italian and American legal systems. Historical and constitutional influences on Italian and American legal systems. Differences and similarities in the merger process. Comparison of FIAT Chrysler and ExxonMobil mergers.

The protection of executory contracts in restructuring proceedings - Dejoux-Pasdeloup, Lea Francoise Paulette (Mikolas Romeris University, 2024)
This thesis focuses on the relationship between contract law and corporate insolvency law as it investigates the idea and protection of executory contracts within restructuring proceedings. However, preserving these agreements frequently necessitates taking legal action against established contract law tenets like the freedom of contract and the duty to perform. The study looks at how difficult it can be to keep debtor and creditor interests in balance, especially when there are disruptions brought on by insolvency. The study suggests ways to improve the efficacy of restructuring proceedings by analysing the EU Directive on restructuring and insolvency, contrasting practices in various jurisdictions, and evaluating the impact on stakeholders. The goal of this study is to protect the rights of all parties involved in corporate restructuring while advancing the creation of legal frameworks that facilitate effective restructuring.
Keywords: Creditor; Cross-border Insolvency; Darbuotojai; Debtor; Employees; Insolvency; Kreditorius; Nemokumas; Restructuring proceedings; Restruktūrizavimo bylos; Skolininkas

The Influence of Corporate Sustainability Laws on Multi-Stakeholder Initiatives to Eliminate Forced and Child Labour in Supply Chains - Fanou, Temisan (McMaster University, 2024)
An array of governance initiatives has emerged to address forced labour and labour exploitation in global value chains (GVCs). Drawing on the transnational business governance interactions theoretical framework, as well as Timothy Bartley’s place-conscious transnational governance model, this thesis examines the interaction between two of these hybrid forms of governance: multi-stakeholder initiatives and corporate sustainability laws. I conduct a case study of the cocoa sector, and specifically of the multinational company, Nestlé, using multiple qualitative research methods including legal analysis, key informant interviews, and documentary analysis. My research suggests that the layering of corporate sustainability laws, and particularly the French Duty of Vigilance Law, on top of CSR and MSIs in the cocoa sector, is not addressing the governance gap that permits corporations to evade accountability for human rights abuses in their supply chain. I find that the introduction of corporate sustainability laws may have contributed to a decrease in Nestlé's efforts to address labor violations in certain areas, while in others, it appears to have supported the continuation of existing practices. This raises implications for the continuous efforts in various jurisdictions to introduce these laws as a solution to the shortcomings of private, voluntary rule-making systems. Further research is required to explore how these governance mechanisms are interacting in other sectors, in companies of different sizes, and within various types of MSIs. This will help identify the factors that influence interactions and shed further light on the path forward for policymakers.

Squaring up with workplace bullying - Naidoo, Natashia (University of Pretoria, 2024)
Workplace bullying is not considered a form of harassment that is commonly acknowledged nor does it attract specific legislative protection. The aim of this mini-dissertation is to ascertain the degree to which victims of workplace bullying are protected by South African labour legislation and whether other measures are necessary to ensure that employees are adequately protected. A comparative analysis between South Africa and the United Kongdom's legislative frameworks that governs workplace violence and harassment and, by implication, bullying is a critical aspect of this mini-dissertation.

Taxing the digital economy: Options available for African countries - Oluwatuyi, Oluwasikemi (University of Victoria, 2024)
Tax authorities have always assessed and enforced taxes based on the physical address of businesses over the years. Nevertheless, the idea of tax jurisdiction has taken on a new meaning with the development of information and communication technology, and its profound impact on every facet of human existence – including but not restricted to trade and business. This development has undoubtedly increased capital mobility, especially in corporate form, and exposed more the weaknesses in national tax laws by enabling the artificial relocation of important economic components and potential exemption from taxes. Since it is getting harder to separate the digital economy from the rest of the economy for taxation reasons, the process of digitalization has emerged as one of the primary growth drivers. This expansion, together with aggressive tax planning strategies used by multinational enterprises (MNEs) to move revenues to low-tax jurisdictions and the development of business models requiring less physical presence, has increased the workload for tax administrators; furthermore, it has reduced governments’ capacity to raise funds in the traditional manner. In this regard, I assess how “adequate” the selected African countries’ frameworks are vis-à-vis the ongoing OECD and UN negotiations. Beyond the consultations, I call for a more inclusive and Africanised approach and the need for African countries to improve their tax administration mechanisms.
https://hdl.handle.net/1828/20312
Keywords: Digital economy; International taxation; OECD; Tax

Critical analysis of the institutional framework governing the agreement establishing the African Continental Free Trade Area - Lehlongwa, Thulane Charlo (Stellenbosch University, 2023)
The African Continental Free Trade Area as a flagship project of Agenda 2063 represents renewed attempts by the African Union to drive the continent closer to its economic integration ambitions, which can be formally traced back to the adoption of the African Declaration on Cooperation, Development, and Economic Independence, and later the Treaty Establishing the African Economic Community. Building on these frameworks, the AfCFTA seeks to, amongst others, advance intra-African trade by creating a single market for goods and services facilitated by the movement of persons, promoting sustainable and inclusive socio-economic growth, creating a liberalised market for goods and services, and promoting industrial development. Central to the attainment of the objectives of the AfCFTA is a well-functioning and effective institutional framework at a continental, regional, and national level all well-integrated to facilitate and oversee its implementation. The strengthening of regional and continental institutions to effectively lead and drive Africa’s transformation agenda has also been recognised by Agenda 2063 as a key enabler to this end. The demise of previous African integration efforts has mainly been attributed to the weakness of regional and continental organs to be able to effectively oversee and administer the implementation of continental programmes by the countries. This thesis appraises the institutional framework established to oversee the implementation, administration, facilitation, and monitoring of the AfCFTA, and this is considered against the broader African Union institutional framework and the regional economic communities. Although vastly different, the thesis further considers the experience and best practices from the European Union regional integration model to draw lessons and with a view to reforming and integrating African continental and regional bodies to be able to effectively oversee key initiatives including the AfCFTA. Finally, the thesis considers some of the work already initiated by the AU to review and reconfigure the extant continental bodies and then recommends some key interventions to reinforce and better integrate the institutional framework of the AfCFTA with the existing continental and regional frameworks.
Keywords: AfCFTA; African Continental Free Trade Area; Dispute resolution; Economic integration; Free Trade; International economic relations

The impact of exchange platforms on the security of European markets - D'Alessandro, Francesco (LUISS Guido Carli, 2023)
Exchange platforms listed on European markets: financial contamination? The Luna collapse: present-day exposé. Aògorithmic stablecoins. The Luna project and the Terra ecosystem. Legal framework of a billion-dollar scam. Class action lawsuits. National and European implications of such actions. Misleading advertising (binance's liability) and culpa in eligendo. Exchange platforms listed on European markets: financial contamination? Parallels between shares and cryptocurrency investments: lack of transparency giving rise to bubbles. InvestVoyager case study. FTX case study. Positive law and new horizons. DeFi self-regulation: AML compliance and exchange platforms. The proposal of MiCA regulation (markets in crypto-assets). Payment systems directive 2 (PSD2). Directive 2009/110/EC on e-money. Potential solutions (proposals). External audit of smart contracts: a comprehensive examination-technical and legal perspectives. Digital euro. Establishment of a national or European commission: risks for consumers and comparative research. Regulation of exchanges and enforcement of transparency obligations.

Attaining effective and speedy resolutions of unfair dismissal disputes in Lesotho: An explorarion of possible lessons from South Africa - Ntaitsane, Mamolefi Anacletta (National University of Lesotho, 2023)
National Manpower Development Secretariat
Keywords: Labour dispute; Lesotho; Resolution mechanisms; Unfair dismissal disputes

The efficacy of commercial arbitration, law and practice Lesotho - Thethe-Chitja, Makabelo (National University of Lesotho, 2023)
The success of commercial arbitration law and practice is achieved as a result of several factors. The purpose of the study was to investigate whether efficacy of commercial arbitration, law and practice in Lesotho is hindered by the legal framework which does not conform to the United Nations Commission Trade Law on International Commercial Arbitration, UNCITRAL Model Law. Examining such other factors as support of the courts and government, the study specifically investigated the impact of lack of education about commercial arbitration for the business community and unregulated arbitrators on the efficacy of the commercial arbitration, law and practice in Lesotho. With the use of the desk reviews and interviews as data collection methods for this study, the evidence obtained has revealed that efficacy of the commercial arbitration, law and practice in Lesotho is hampered by the law which is outdated and inconsistent with the UNCITRAL Model law. As such, support for the mechanism by the courts has been found to be at stake or adversely affected. Lack of support from the government and that of awareness campaigns about the mechanism for the business community have also been noted for constraining the efficacy of the commercial arbitration, law and practice in the country. Further noticeable from the findings include limited commitment from the legal profession and unregulated arbitrators, both of which could have significantly obstructed the mechanism. The study thus concludes that there is an urgent need for law reforms and concerted commitment from the relevant stakeholders to help towards achieving efficacy of the commercial arbitration, law and practice in Lesotho.
Keywords: Arbitrage; Arbitragem; Arbitration; Commercial Arbitration; Lesotho

The protection of EU technological sovereignty in the area of foreign direct investments: legal challenges after the EU regulation 452/2019 - Vecchio, Giuseppe (LUISS Guido Carli, 2023)
EU’s competence over FDI: European technological sovereignty. Definition, origins, and scope of EU foreign investment law. EU competence over foreign direct investments. European technological sovereignty. Regulation 452/2019–screening mechanisms in national legislation with a focus of the Italian regime. Structure of regulation 452/2019. Implementation in national legislation. The screening regulation as a tool to enforce technological sovereignty. EU technological sovereignty in practice. First and second annual report on the screening of foreign direct investments into the Union. A first appraisal of the problematic interplay between FDIs and technological sovereignty.

Holding multinational corporations liable for their transnational environmental harms : a search for global liability - Roxburgh, Craig (Stellenbosch University, 2023)
For several decades, environmentalists have raised the alarm regarding the impending environmental catastrophe that results from the Anthropocene. Much attention has been given to the role that States play in contributing to ecological damage being wrought upon the Earth. However, we have only looked at the environmental destruction perpetrated by multinational companies (“MNCs”) in the past decade. Natural disasters like the Deepwater Horizon explosion have placed MNCs' dangerous impact on the environment in sharp relief. At the same time, revelations in the Carbon Majors Report and global litigation quantify the damage MNCs cause to the environment. Multinational companies (“MNCs), as a result of globalisation and trade liberalisation, are powerful entities within the global economy. Despite their size, MNCs remain primarily unregulated in international human rights law. Debates regarding who bears the duty for human rights intersect with a battle of political will between the Global North and Global South for developing binding human rights duties for MNCs. As a result, they can commit environmental harm, especially in the Global South, with relative impunity due to a lack of effective liability mechanisms. The doctrine of separate legal personality creates specific issues for holding MNCs liable for environmental harms in the Global South. Domestic courts in home States struggle to exercise jurisdiction over the environmental harms MNCs commit. In contrast, systemic barriers in host States create situations where victims are unable to seek redress within their State. To address these concerns, this thesis proposes a global liability regime founded on the principle of integrated regulation. This regime will utilise regulation at the institutional, national and international levels to enforce the environmental obligations of MNCs, rooted in the right to a healthy environment. This gives rise to multiple intersection human rights obligations which will regulate the behaviour of MNCs. This thesis recognises that such a framework requires a drastic reform in how the law and companies are conceptualised. However, such a reform would have wide-reaching implications for vindicating human rights violations.
Keywords: Corporations; Developing countries; Environmental law; Environmental protection; International business enterprises; International cooperation; Liability for environmental damages; Offenses against the environment

Critical Review of the Adoption of the Uncitral Model Law on International Commercial Arbitration in Africa - Mboya, Rachael A. (University of Nairobi, 2023)
Accepted: 2024-09-28T07:32:41Z

The concept of separate legal personality in South African company law: A critical examination of its origins, developments and current application - Myeni, Siphosethu (University of KwaZulu-Natal, 2023)
Section 19(1) of the current Companies Act 71 of 2008 states that once a company is incorporated in accordance with this Act, it is considered as a juristic person and exists indefinitely until its name is removed from the companies register. It exists independently from its shareholders and controllers. This effect grants the company with characteristics of a natural person. This analogy implies complete independence of the company. However, this concept finds refuge from the English legal system and was later adopted by South African company law. This notion provides some legal protection to businesses and shields their owners from personal liability for the company's debts and commitments. Companies can use this to enter new markets, reduce their taxes, and take advantage of advantageous business environments. Furthermore, this doctrine promotes joint ventures and partnerships among enterprises from many countries, allowing them to share resources and risks. As a result, this allows international enterprises to benefit by conducting international transactions, expanding abroad, and entering contracts in foreign countries. However, like any other concept, it is susceptible to abuse. Individuals take advantage of it to benefit themselves. This is detrimental to the significance of this doctrine. This dissertation aims to look deeply into this concept, by examining its origins and influence throughout the years and during its current application in the South African legal framework and highlight instances where this doctrine will be set aside. This will be conducted by fully analysing Salomon’s case and the influence it has over current company law. More importantly, the author will further examine the significance of this doctrine in modern company law. This will be done by testing the application of this doctrine to modern corporations and challenges they face.

Anti-Money laundering developments : A comparative appraisal - Schlebusch, Maria Elizabeth (Marlize) (University of Pretoria, 2023)
The objective of this study is to understand and explore the rapid pace at which ML has evolved and the global and local impact thereof.

The law applicable to an international commercial contract : a comparative study of private international law of contract in South Africa and South Korea - Setlhabi, Godiraona (University of Johannesburg, 2023)
Please refer to full text to view abstract.

Free movement of goods and new agreements in the aftermath of Brexit - Police, Cecilia (LUISS Guido Carli, 2022)
The main principles of EU internal market vs the new UK internal market: a background. The internal market of the European Union. UK membership: accession to the European economic community in 1973. The nature of the EU internal market and the free movement of goods. The UK internal market after the internal market act 2020. The EU common commercial policy and the post-Brexit scenario. Brexit: new agreements and legal framework. EU-UK post-Brexit relationship: a new framework for a new partnership. Brexit history and the question of sovereignty. Brexit history: the timeline. Brexit and the withdrawal agreement. Brexit and Northern Ireland protocol. Brexit and trade: perspectives on a new partnership. Brexit and trade: trade and cooperation agreement. Trade and cooperation agreement: EU-UK trade relations, institutional and governance structures. Preliminary remarks. Analysis of the TCA: trade in goods provisions. 0,0 agreement: zero tariffs, zero quotas and rules of origin. The TCA: technical barriers to trade (TBT). The TCA: sanitary and phytosanitary standards (SPS). The TCA: the principle of mutual recognition. Level playing field (LPF). The Northern Ireland protocol and the trade in goods regime. TCA’s main concerns and application issues. TCA dispute settlement mechanisms. Some conclusive remarks on TCA provisions.

The conclusion of contracts by electronic agents in the age of the Fourth Industrial Revolution : a South African perspective - Doughan, Albert Nana (University of Johannesburg, 2022)
Please refer to full text to view abstract.
Keywords: Commercial law; Contracts; Electronic data interchange; Industry 4.0

The role of good faith in South African contract law - Govender, Tashri (University of KwaZulu-Natal, 2022)
This research paper seeks to address the role that good faith plays in South African contract law by first discussing its origin and then chronologically tracing its position from pre-1994 to today. The judgements of both the Supreme Court of Appeal and the Constitutional Court will be unpacked, as a means to understand the development of good faith over the years. The position that good faith plays in foreign jurisdictions will also be discussed, for the sake of achieving a universal understanding of how good faith is perceived around the world. The research concludes by placing good faith in its current role and context in South Africa, and also proposing a way forward.
Keywords: Bona fides; Contract Law

A critical analysis of the institution of business rescue proceedings during liquidation proceedings - Krishundutt, Sanam (University of KwaZulu-Natal, 2022)
South Africa is currently undergoing harsh economic times, and as such, many companies are feeling the brunt of the situation. As a result, these companies begin to trade at a loss and are left without any other option but to liquidate their affairs in order to pay off creditors. However, with the development brought by the Companies Act 71 of 2008 (“the Act”), business rescue was introduced. Business rescue is an alternative to liquidation and it allows the company to undergo rehabilitation and continue trading if certain requirements are met. Chapter 6 of the Act aims to assist businesses in providing some sort of relief in the form of business rescue to provide them with the breathing space that they require to try and become a viable business again. Just like any new formulated concept, it is susceptible to abuse. Many companies that are already under liquidation are suspending their liquidation in favour of business rescue, despite, in some instances, the liquidation order having already been granted against the company. The Covid-19 pandemic has made the question of whether a business can suspend liquidation proceedings in favour of business rescue more prevalent as the pandemic has caused a detrimental financial impact on a number of businesses. Now more than ever businesses find themselves struggling to keep afloat, and as a result many of them have to consider the avenues of liquidation or business rescue. This dissertation aims to look at both liquidation and business rescue proceedings and decipher whether the courts were correct in their decision regarding when business rescue proceedings can be instituted during liquidation proceedings. The importance of taking into account the above is due to the fact that many companies in present day are experiencing financial difficulties, and liquidation or business rescue proceedings are the options that they are left with. However, one has to carefully consider both options, taking into account the company’s financial circumstances. This is of importance, as one needs to establish if there is a reasonable prospect of rescuing the company or not. If there were, then business rescue would indeed be the route to be taken, but if not, then liquidation proceedings would be. However, many companies that have no prospect of being rescued, and that have already opted for liquidation may want to institute business rescue proceedings to delay the inevitable and frustrate creditors, thus leading to the abuse of the newly formulated concept, which has to be curbed.
Keywords: Business failure; Companies Act 71 of 2008; South Africa

A critical analysis of the role, appointment, and powers of a business rescue practitioner - Luthuli, Bayanda Nompumelelo (University of KwaZulu-Natal, 2022)
No abstract provided.
URI: https://researchspace.ukzn.ac.za/handle/10413/20930
Keywords: Corporate rescue regime; Financially distressed companies; Judicial management

The abuse of dominant position in digital markets: Google Shopping case - Moroni, Filippo (LUISS Guido Carli, 2022)
Abuse of dominance in the digital markets. Digital markets. Art.102 TFEU: how can it be applied to digital markets? A global perspective: the evolution of the abuse of dominance in digital markets around the world. Europe: the proposal for a regulation on contestable and fair markets in the digital sector (digital market act). United States of America: a time for reforms. China: a new approach towards digital markets. The Google Shopping case: the first step for competition enforcement in digital markets. The European Commission decision (AT.39740). The general Court decision (T-612/17). The Google case in the US: completely different results. A glimpse into the future: the Google Shopping case under the DMA.
Keywords: Abus de position dominante; Competencia; Competition law; Concurrence; Dominant position; Monopole

The use of blockchain technology in international commercial transactions, with specific reference to secured payments in international contracts of sale - Muza, Chido Teclar Mitchel (University of Johannesburg, 2022)
Please refer to full text to view abstract.
Keywords: Blockchains (Databases); Commercial law; Electronic funds transfers; Export sales contracts.; Foreign trade regulation

Conflict Management over Maritime Territories : Use of ADR in Maritime Disputes: Kenya vs Somalia - Mwala, Natasha Lulia (Universität Wien, 2022)
The recent discoveries of natural resources on both territorial and maritime borders have heightened the probability of conflicts between states specifically in the Horn of Africa and the Greater Lakes Region. As a highly volatile region, conflicts are not a foreign phenomenon which have been plaguing the region since transition to the post-colonial era. It is simple to argue that the cause of disputes is due to the arbitrary borders drawn by the European powers, however, the region is experiencing a contemporary ‘scramble and petition’ with countries racing to exploit and gain over the newfound resources. In addition to this, the rise of nationalist sentiments combined with the burgeoning population and struggle of governments to finance their domestic budgets while trying to reduce borrowing from foreign markets due to the inflation costs which makes it expensive, also plays a key role in the quest to benefit from mineral exploration and excavation. While traditional conflicts rose from land border disputes that escalated to violence especially between border communities, maritime conflicts tend to be handled in legal ways with parties seeking intervention from bodies such as the International Tribunal of the Law of the Sea (ITLOS) and the International Court of Justice (ICJ). Most cases are solved by outright delimitation of the maritime borders rather that joint management of marine land masses or natural resources based on mutual understanding or mutually assured benefits. The recent Kenya-Somalia Maritime dispute is an excellent case study. The aim of this research is to not only show alternative dispute resolution methods that can be used in maritime border disputes but also analyse the switch from pacific means of settlement of disputes to judicial intervention of the court. It begins by looking at the evolution of land border disputes between the two states, touches on the maritime dispute and their diplomatic, economic and security relationship. It further critically analyses the points of view of the two countries and the court’s ruling. Finally, it examines alternative dispute settlement mechanism that could have been used.
Keywords: ICJ; Joint maritime agreement; LOS; Maritime boundary dispute; Maritime délimitation; Memorandum of understanding

The Processes of Democratization and Economic Development in Africa: A Case Study of the Democratic Republic of Congo (DRC) Since 2006 - Otshudi Talo, Esperance (Near East University, 2022)

A legal comparison on the effectiveness of judicial management in Botswana against business rescue in South Africa - Topi, Sharon (University of Johannesburg, 2022)
Please refer to full text to view abstract.

The inclusion and assessment of climate related and environmental related risks in the banking industry: the UniCredit case. - Gioia, Giovanni Luigi (LUISS Guido Carli, 2021)
The nexus between climate-related risks and financial risk. From nuclear to climate apocalypse. The turning point: Paris agreement and UN 2030 agenda for sustainable development. The VUCA world. The European Union as pioneer of ESG revolution. Climate-related risks in the banking sector. The EBA framework of ESG risk for financial institutions. The principles for responsible banking. Environmental-related risk assessment. The mispricing of the environmental-related risks. The environmental-related disclosure as a risk mitigation tool. How do UniCredit assess, monitor and mitigate climaterelated risks. UniCredit’s financial risk management framework. Comparison with KPMG benchmark.

A critical analysis of the effect of the moratorium on property owners - Beekarun, Yasthil (University of KwaZulu-Natal, 2021)
No abstract provided.
Keywords: Business rescue

A comparative analysis between the Turkish Financial Reporting Standard for large and medium-sized entities and the OHADA accounting system - Diallo, Amadou Thierno (Sakarya Üniversitesi, 2021)
The rapidly growing bilateral and multilateral economic relationship between Turkey and African countries leads to the necessity of understanding each other's business and financial environment. Therefore, the accounting system as a fundamental tool for organizing and disseminating financial information should be accessible and understood by business actors and other stakeholders in these areas. Furthermore, the lack of study related to this subject has led us to carry out this comparative analysis between the two accounting systems by comparing financial statements prepared under each one and analyzing their main similarities and differences. The main purpose of this study is to highlight major differences and similarities between the SYSCOHADA and the FRS for LMSE. Also, the study is aimed to get a good understanding of both accounting sets and help practitioners and businessmen, and women operating in these places to have a good knowledge of the accounting regulations related to each country. On a topic basis and based on financial statements prepared following the SYSCOHADA rules and restated to be adapted to the FRS for LMSE, all main differences and similarities were thoroughly analyzed. Following the case study and the thematical analysis of different accounting topics, it can be understood that the two accounting sets differ to some extent due to philosophical approach on some topics such as the prudence principle where the SYSCOHADA, contrary to the FRS for LMSE, does not allow the recognition of potential profit resulting from currency translation gains related to receivable and payables until such profit becomes certain. However, these two sets also share some major similarities due to their proximity in some way to the IAS/IFRS. The effect of the main differences between the two sets can be noticed in the restated financial statements. The annual net income following the FRS for LMSE increased compared to the initial annual net income in the SYSCOHADA. Also, total assets and liabilities restated following the FRS for LMSE have decreased compared to the SYSCOHADA financial statements. Türkiye ile Afrika ülkeleri arasında hızla büyüyen ikili ve çok taraflı ekonomik ilişkiler, birbirlerinin iş ve finans ortamını anlama zorunluluğunu doğurmaktadır. Bu nedenle, finansal bilgilerin düzenlenmesi ve yayılması için temel bir araç olarak muhasebe sistemi, bu alanlardaki iş aktörleri ve diğer paydaşlar tarafından erişilebilir ve anlaşılabilir olmalıdır. Ayrıca bu konuyla ilgili çalışma eksikliği, iki muhasebe sistemi arasında bu karşılaştırmalı analizi, her biri altında hazırlanan finansal tabloları karşılaştırarak ve temel benzerlik ve farklılıklarını analiz ederek yapmaya yöneltmiştir. Bu çalışmanın temel amacı, SYSCOHADA ve BOBİ FRS arasındaki önemli farklılıkları ve benzerlikleri vurgulamaktır. Ayrıca, çalışma hem muhasebe standartları iyi anlamak hem de uygulayıcılara ve bu yerlerde faaliyet gösteren iş adamlarına her bir ülkeyle ilgili muhasebe düzenlemeleri hakkında iyi bilgi sahibi olmalarına yardımcı olmayı amaçlamaktadır. Konu bazında ve SYSCOHADA kurallarına göre hazırlanmış ve BOBİ FRS' ye uyarlanmak üzere yeniden düzenlenen mali tablolara dayalı olarak, tüm temel farklılıklar ve benzerlikler kapsamlı bir şekilde analiz edilmiştir. Vaka çalışması ve farklı muhasebe konularının tematik analizi sonucunda, iki muhasebe setinin bir ölçüde felsefi yaklaşım nedeniyle ihtiyat ilkesi gibi bazı konularda farklılık gösterdiğini anlaşılmaktadır. SYSCOHADA, BOBİ FRS'nin aksine alacak ve borçlara ilişkin kur farkı kazançları kaynaklanan potansiyel kârın kesinleşene kadar muhasebeleştirilmesine izin vermemektedir. Bununla birlikte, bu iki muhasebe seti, UFRS/UMS'ye bir şekilde yakın olmaları nedeniyle bazı önemli benzerlikleri de paylaşmaktadırlar. İki sistemin temel farkların etkisi, yeniden düzenlenen mali tablolarda fark edilebilir. BOBİ FRS'yi takiben yıllık net gelir, SYSCOHADA'daki yıllık net gelire kıyasla artmıştır. Ayrıca, BOBİ FRS'yi takiben yeniden düzenlenen toplam varlıklar ve yükümlülükler, SYSCOHADA finansal tablolarına kıyasla azalmıştır.
Keywords: Accounting standards; Accounting systems; Büyük ve orta boy işletmeler için finansal raporlama standardı; Comparative analysis; Financial reporting standard for large and medium size enterprises; Financial reporting standards; Finansal raporlama standartları; Karşılaştırmalı analiz; Muhasebe sistemleri; Muhasebe standartları; Turkish Financial Reporting Standards; Türkiye Finansal Raporlama Standardı

Cryptocurrencies in an insolvent estate - Du Plessis, Shandi (University of Johannesburg, 2021)
Please refer to full text to view abstract. LL.M. (Commercial Law)

Smart contracts : the Fourth Industrial Revolution and private international law - Dwamena, Elizabeth (University of Johannesburg, 2021)
Please refer to full text to view abstract. LL.M. (International Commercial Law)

The impact of Covid-19 on labour law protection for Uber drivers - Gxabu, Mampho Aphelele (University of Johannesburg, 2021)
On 15 March 2020 the President of the Republic of South Africa announced a nationwide lockdown. The unpredicted pandemic dictated that extraordinary measures be put in place, which resulted in the country coming to a total standstill. Consequently, there was an alarming decline in economic activities and therefore government had to introduce measures to mitigate the impact of COVID-19 on employers and workers.

The tax implications of intellectual property: an overview of the development of the law pertaining to deductions - Khan, Ilhaam (University of KwaZulu-Natal, 2021)
No abstract available.

The tripartite free trade area: towards a comprehensive African economic community with a particular focus on SADC - Mabinza, Siqhamo (University of KwaZulu-Natal, 2021)
No abstract available.
Keywords: Africa; GATT; Multilateral trading systems; Regional Trade Agreements (RTAs); SADC; Southern African Development Community; WTO

The principle of party autonomy in the HAGUE principles on choice of law in International Commercial Contracts : lessons for Chinese, Russian and South African Private International Law - Manganye, Makhanani Annastesia (University of Johannesburg, 2021)
It is no secret that there has been an increase in international trade in recent decades. Natural and juristic persons have taken it upon themselves to trade both domestically and internationally. As international trade increases so too do the conclusion of international commercial contracts. When individuals enter into an international contract, one particularly important issue, and one that should be foremost in the minds of the contracting parties, is which legal system will govern their agreement? Therefore, a significant factor to any international commercial contract is whether the parties have the freedom to choose the law applicable to their agreement and to choose the court that will adjudicate upon their contractual disputes, and if so, to what extent may the parties exercise their freedom of choice?... LL.M. (International Commercial Law)
Keywords: Commercial policy; Commercial treaties; International trade

The impact of the Trade-Related Aspects of Intellectual Property Rights (TRIPS) on the right to health and the right to development: a study of the implementation of TRIPS in Zimbabwe - Munemo, Ropafadzo Blessing (University of KwaZulu-Natal, 2021)
The right to health and the right to development are intertwined socio-economic rights that affect the well being and growth of a country’s populace. Most developing and least developed countries face challenges in ensuring access to essential medicines vis a vis the realisation of the right to health and full potential of development. Patents, provided for under the TRIPS Agreement are partly to blame for the lack of access to essential medicines as they account for the excessive pricing of medicines. Zimbabwe being a developing country currently facing dire economic and political challenges but being obliged under the International and Regional Human Rights Conventions it subscribed to, has to ensure the progressive realisation of the right to health and development. However, as a member of the TRIPS Agreement, there are limitations to the country’s ability to ensure access to medicines and healthcare for developmental purposes. This thesis has outlined the problematic provisions of the TRIPS Agreement and Zimbabwe’s attempt to use the flexibilities provided to its advantage. Zimbabwe has only put into use the flexibility of compulsory licensing and parallel importation to a limited extent; hence the recommendation that even though the country has domesticated the Agreement to its advantage, the country needs to explore other flexibilities comprehensively and promote the realisation of the rights to health and development.
Keywords: Access to medicine; Health care costs; Intellectual property; Public health; TRIPs; Trade tariffs; Zimbabwe

An analysis of the consequences of a business rescue moratorium on legal proceedings on property owners - Ngubane, Samukelo Siyanda (University of KwaZulu-Natal, 2021)
It has been over a decade since the Companies Act 71 of 2008 introduced business rescue proceedings which provided for the rescue of financially distressed companies. This procedure replaced the then statutory procedure of judicial management under Companies Act 61 of 1973. The business rescue proceedings begin with the general moratorium or stay on legal proceedings against the company or its property. This has a consequence that any claims against the company may only be enforced with the consent of the business rescue practitioner or the leave of the court. However, the courts continue to grapple with the interpretation, effect, and application of the key elements of business rescue provisions while always striving to accord respect to the legislative intention of business rescue as set out in section 7(k) of the Companies Act 71 of 2008. After a decade since its introduction, it is an opportune time to ascertain whether the business rescue proceedings is an effective corporate rescue procedure suitable to the modern-day demands of the South African economy. The research analyses the effect and the consequences of the moratorium on the rights of property owners. The moratorium has the effect that companies are given temporary immunity to actions brought by creditors which would have been due and enforceable. In this regard, the property leased by the property owner remains occupied by the company during business rescue proceedings as the property owner is barred by the moratorium to institute legal proceedings against the company. Further, when the repossession of the property is not possible and the rental due or installment is not payable by the company, the business rescue proceedings encroaches on the right of the property owners. The purpose of the research is to highlight the effect of the moratorium on the lease agreement between the company and property owners and the possible protection of the property owners’ rights. The study includes a critical analysis of judicial decisions on the moratorium, together with a discussion of the legal position in comparable foreign jurisdictions. In my conclusion, based on the findings, the business rescue is not free from imperfection. Therefore, I recommended that the legislature amend some parts of Chapter 6 of the Companies Act 71 of 2008.
Keywords: Companies Act 71 of 2008; Corporate rescue procedure; Financially distressed companies; South Africa; Stay on legal proceedings

A Third World approach to the role of South Africa, Nigeria and Kenya in the multilateral trading system - Nzimande, Nosiphiwo (University of KwaZulu-Natal, 2021)
No abstract provided.
Keywords: GATT; General Agreement on Trade and Tariffs; International Trade; Kenya; Nigeria; Regional Trade Agreements (RTAs); South Africa; WTO; World Trade Organization; World trade

Takeover and shareholders' agreements - Sabatini, Federico (LUISS Guido Carli, 2021)
The OPA. Notions of takeover bids. Recognising and distinguishing the various forms of control within a company. Type of takeover bid. Subsequent defence techniques. The US control market and details of M&A and tender offers. Bids and acquisitions in China. Comparative European case studies. Shaldeholders' agreements. Regulatory sources and definition of covenants. Concerted action. Takeover obligations arising from concerted action. Cases. The Fondiaria-Sai case. Unipol-BNL. Other case of exemption.

The dispute board in international construction contracts - Nunziata, Martina (LUISS Guido Carli, 2020)
The dispute board as an alternative dispute resolution mechanism in international construction contracts. The functioning of the dispute board. Issues related to the legal nature and the enforcement of the final determination. Evaluation and familiarity with the mechanism of the dispute board. The Italian case and the distrust towards the development of "private justice systems".

The choice of non-state law in international commercial contracts - Abdullah, Humaira (University of Johannesburg, 2020)
When a dispute arises in relation to an act, person or property that is connected to more than one country, such dispute is governed by the rules of private international law, more commonly referred to as the “conflict of laws”.1 The term conflict of laws essentially means that the dispute in question will be governed by the national law of a country while having a connection to a foreign country,2 and is relevant to this discussion as the election of non-state law is an important aspect found within private international law. In order to determine whether or not such laws may be applied, courts usually look at the conflict of laws rules of that particular country... LL.M. (International Commercial Law)
Keywords: Commercial law; Conflict of laws; Contracts (International law)

The development of the parol evidence rule and its impact on the interpretation and drafting of contracts - Dhlamini, Tshogofatso Elisa (University of Johannesburg, 2020)
Please refer to full text to view abstract. LL.M. (Commercial Law)

A critical discussion of the affected parties in business rescue proceedings - Gayadin, Kashmita (University of KwaZulu-Natal, 2020)
Abstract available in PDF.
Keywords: Companies Act 71 of 2008; Creditors; Financially distressed companies; Shareholders

The law applicable to liability arising from the use of selfdriving cars in the wake of the Fourth Industrial Revolution : a global comparative analysis - Kyeremateng, Joshua Godwin (University of Johannesburg, 2020)
This study explores the liability associated with the use of autonomous vehicles. With the increase in efforts by automobile industries to manufacture driverless cars, the issue of liability occupies the front seat of the discussion. A major benefit of autonomous and connected vehicles is their potential to ameliorate, if not eradicate, avoidable accidents on roads. Currently, it is estimated that 90% of road accidents are caused by human error. The epoch of driverless vehicles, where the narrative will drastically change, is upon us. This means a shift away from human liability to machine liability, since these technologies have in-built algorithms to ensure autonomous decisions by the vehicle. Product liability becomes crucial in the wake of driverless cars. The gradual and ultimate shift of liability from the traditional human driver to the machine ‘driver’ coupled with the cross-border sale of driverless vehicles provide justification for scholarly attention. Accidents may now be attributed to technological error and not human mistake. Conflict of law issues become central in instances where manufacturers and users live in different parts of the world... LL.M. (International Commercial Law)
Keywords: Automated vehicles; Commercial law; International law; Products liability

The role of the Southern African Development Community (SADC) and the Economic Community of West African States (ECOWAS) in facilitating continental integration - Luthuli, Isaac (University of KwaZulu-Natal, 2020)
The dissertation examines the role the Southern African Development Community (SADC) and the Economic Community of West African States (ECOWAS) can play in facilitating the political and economic convergence of the African Union (AU) member states. The developmental challenges facing Africa in spite of its wealth of human and natural resources is poignant. The genesis of this problem can be traced to the history of colonialism and the wave of independence in the continent in the late 1950s. Arguments have been put forward to suggest that one of the most viable ways of promoting Africa’s development is by developing and promoting intra-continental trade which can be possible through continental integration. The specific areas reviewed are regional stability and how intra-regional trade and investment is used to promote economic convergence. Africa's need for political and economic integration at a continental level is further sustained by the assumption that neocolonialism can be blamed for the weakness of structures in African states. Some scholars agree on the idea that regionalisation is often seen to offer a possibility to respond to the challenges of globalization. This impact nevertheless is dependent on the relation between globalisation and regional sentiment. Regional integration implies a form of interdependence among nation-states. Such interdependence leads to an establishment of regional integration arrangements between sovereign states within a geographical space. These agreements are shaped formally and there is a commitment to work together in order to realise political and socio-economic benefits. This study maintains that in order to achieve effective integration of the continent, Nigeria and South Africa as case studies, as continental giants have a key role to play to this end and as members of ECOWAS and SADC respectively. It is argued here that both the SADC and ECOWAS as sub-continental blocks have made some notable and commendable progress in developing policies for trade liberalization and economic integration, this, however, is not enough as such policies are also pertinent at a continental level. The study found that SADC and ECOWAS as regional blocks can play a role in aiding the continent to achieve a trade liberalization to achieve continental economic development.
https://researchspace.ukzn.ac.za/handle/10413/18708
Keywords: African integration; ECOWAS; Economic Development; Economic convergence; Integration; Intra-continental trade; SADC

The role of the locus contractus as a connecting factor in common-law private international law of contract - Madziwa, Cuthbert Simbarashe (University of Johannesburg, 2020)
Global trade has consistently been on an upward trajectory over the past few decades. In 2001, the International Monetary Fund (IMF) estimated that over the course of the previous twenty (20) years world trade had grown at an average rate of six (6) percent per annum, double as fast as world output.1 A substantial component of global trade consists of cross-border transactions. It was projected that between 2010 and 2022, the number of global transactions would double from three (3) to six (6) trillion per year.2 These volumes of global trade naturally entail an enormous number of cross-border commercial contracts, which often result in disputes over defective goods or services, payment or, delays... LL.M. (International Commercial Law)
Keywords: Commercial Law; International law

Balancing the rights of creditors and consumers when a home is sold in execution: what procedures should be followed? - Mazubane, Zamanguni Sithabile (University of KwaZulu-Natal, 2020)
The sale in execution of theprimary residence of a consumer has numerous implications. This is especially in light of section 26 of the Constitution of the Republic of South Africa, 1996(‘Constitution’) which gives people the right to adequate housing and to not be arbitrarily evicted from their homes. The enactment of the National Credit Act 34 of 2005(‘NCA’) which aimsto balance the rights of creditors and consumers also impacted the procedure to sell homes in execution. In particular, section 129 of the NCA has pre-enforcement procedures whilst section 130 allows credit agreements to be reinstated if consumers can pay the overdue amounts and other costs in full. In addition, amendments were made tothe Magistrates’Court Rules and the Uniform Rules of Court regarding the sale of consumers’homes.The new requirements introduced by the NCA and procedures introduced by thecourt rules resulted in a great deal of confusion with different courts and judges adopting different approaches. Eventually, several matters which sought to sell consumers’homes in execution were heard in Absa Bank v Mokebe and Related Matters 2018 (6) SA 492 (GJ)(‘Mokebe case’). Van der Linde Jofthe Gauteng Local Division of the High Court, used the power granted in section 14(1)(b) of the Superior Courts Act 10 of 2013 to, in consultation with the Judge President, discontinue the hearing of the matters before him and refer the mattersto the full bench of the Division.In essence, the court held that a uniform approach must be taken by the judges of this Division regarding how they handle foreclosure matters. This thesis investigates the procedure that creditors should follow before they are entitled to sell consumers’ homesin execution. In order to do this, this thesis will examinethe Constitution, NCA, court rules, practice notesand case law. More specifically, the persons that are the focusof the investigation are creditors that have a security right in the form of a mortgage bond over the home,versus consumers who have become overindebted and are no longer able to meet their obligations under the loan agreement that was entered into with the creditors. There cent landmark Mokebe case is examined in depth to determine what the current law is and how it can be improved.Furthermore, the effect of the Mokebe case inother High Court Divisions in the country will be briefly discussed.Lastly, this thesis sets out what consumers can do to prevent their homes being sold on publicauction especially after they default in their payments. This thesis will show that the procedure to sell homes in execution has drastically changed from the pre-constitutional to the current constitutional dispensation. However, it is submitted that the procedures can still be improved upon. This is because the right to adequate housing is an important socio-economic right which has been undervalued and overlooked. The courts have previously allowed execution of homes without considering the circumstances of consumers. The court rules allowed for this as the contractual rights of creditors were held at a higher standard than the socio-economic rights of consumers. It is argued that in the light of the NCA and its aims, there must be an appropriate balancing of the rights of creditors and consumers to create just outcomes. If we are to truly create a society based on ‘human dignity, the achievement of equality and the advancement of human rights and freedoms’ as expressed in the founding values of South Africa’s Constitution and reiterated to a large extent in the NCA; foreclosure laws must also reflect that vision.
Keywords: Consumers; Creditors; Execution; Foreclosure; Human dignity; Mortgage bond; National Credit Act 34 of 2005

A critical analysis of the subcontractor’s builder’s lien - Mdletshe, Sithandiwe Samukelisiwe (University of KwaZulu-Natal, 2020)
This research paper looks at the South African common law right to lien as it currently stands as the only compensatory remedy for a construction subcontractor in the event of non-payment by the main contractor. The nature and scope of the builder’s lien in this regard will be analysed and its limitations will be highlighted. Accordingly, having critically considered a potential alternative remedy, an unjustified enrichment claim, for the subcontractor, this research paper will illustrate that there is insufficient protection for an unpaid subcontractor in our legal system. Hence, there is a need for our common law builder’s lien to be developed into a statutory builder’s lien. An analysis of foreign jurisdictions legal position, in particular Canadian law, with regard to the construction subcontractor and the right to lien as a remedy has a commendable statutory measure in place to assist a subcontractor by attempting to prevent such a financial predicament and if it nonetheless still occurs, that in the event of non-payment, the subcontractor is adequately protected. This research project proposes that our legal system should take influence from the Canadian legal system and be developed in accordance with our legal framework in order for construction subcontractors to also have sufficient and effective protection under our legal system.
Keywords: Builder’s lien; Contract; Liability; Subcontractor; Unjustified enrichment

The impact of cryptocurrencies on the general powers and duties of insolvency practitioners - Naidoo, Sidasha (University of Johannesburg, 2020)
Please refer to full text to view abstract. LL.M. (Commercial Law)

The implication of the moratorium on lease agreements in business rescue - Nqwata, Sibahle (University of Johannesburg, 2020)
The purpose of the Companies Act1 is, amongst others, to “provide for the efficient rescue and recovery of financially distressed companies, in a manner that balances the rights and interests of all relevant stakeholders.”2 Business rescue means facilitating the rehabilitation of a financially distressed company by providing temporary supervision of the company, a temporary moratorium on legal proceedings against the company in business rescue and the development and implementation of the business rescue plan.3 As a result of the moratorium, the legal proceedings against the company may only be instituted with the consent of the business rescue practitioner or with the leave of the court.4 Thus, the moratorium is the cornerstone of business rescue as it provides a company with an opportunity to operate on a solvent basis.
Keywords: Contracts; South Africa; commercial law

A critical assessment of freedom of choice of law in international commercial contracts - Raissa, Kalenga Kalubi (University of Johannesburg, 2020)
Please refer to full text to view abstract. LL.M. (International Commercial Law)
Keywords: Commercial law; Contracts (International law); Foreign trade regulation

How will the information regulator manage and control advancements in technology to minimise its adverse effects on the protection of personal information? - Ramcharan, Sarika (University of KwaZulu-Natal, 2020)
No abstract provided.
Keywords: Data protection; POPIA; Personal information; Privacy infringements; Privacy protection; Protection of Personal Information Act; Right to privacy; Technology and privacy

How do big data and data analytics impact the external audit ? A critical analysis - Heck, Natascha (Université de Liège, 2019)
The aim of this research is to determine how the application of Big Data and Data Analytics techniques influences the external audit. The impact on the working methods and the audit quality is discussed. Furthermore, the technological maturity of the Belgian and Luxembourgish audit industry is analysed. Therefore, the following research questions are asked: How do Big Data and Data Analytics influence the audit working method? What is the impact of Big Data and Data Analytics on the audit quality? How is the audit risk identification and assessment phase influenced? Which audit risks can be identified? Which tools and techniques do the Belgian and Luxembourgish auditors use and where do they stand? In order to answer the research question, scientific articles were analysed in the context of the literature review. Subsequently, a case study was carried out. Interviews with experts in Belgium and Luxembourg were conducted. The results of the research show that there is high potential to use these technologies in audit. Nevertheless, it is also connected with initial investments and a certain agreement of the clients. There is high potential to enhance the auditor’s effectiveness and efficiency, but the complete impact cannot yet be analysed. The audit quality can be enhanced when qualitative analyses generates audit evidence based on high quality data. The Belgian and Luxembourgish audit industry has just started implementing the technologies.
Keywords: Audit; Big Data; Data Analytics; External Audit

The power of will and choice of law in international contracts - Dazzi, Pietro Giulio (LUISS Guido Carli, 2019)
Party autonomy and sovereignty. Historical developments on party autonomy, the evolution of choice of law. The freedom of choice. The freedom not to choose, absence of choice. Limits to the freedom of choice. Limits to the freedom of choice, an expression of sovereignty. Same functions, different results.

A critical analysis of the effectiveness of the business rescue regime as a mechanism for corporate rescue - Bagwandeen, Kiren Kesh (University of KwaZulu-Natal, 2019)
Almost eight years after the enactment of the business rescue regime under the Companies Act 71 of 2008, and a plethora of judgments which have probed and prodded its provisions, it is an opportune time to ascertain whether the business rescue regime is an effective corporate rescue mechanism suitable to the modern day demands of the South African economy. In the current economic downturn, South Africa can ill afford a repeat show of the failed judicial management system. It requires a modern and effective corporate rescue mechanism that can be utilised in appropriate circumstances as a viable alternative and not merely a precursor to liquidation. This dissertation seeks to provide a critical analysis of the effectiveness of the business rescue regime to ascertain its worthiness as a corporate rescue mechanism.
Keywords: Bankruptcy; Business failures; Corporation law; Insolvency; South Africa

A Comparative Study of ECOWAS and ECCAS towards Implementation of the Abuja Treaty - Nyasembi, Kevin Selassie (University Of Ghana, 2019)
The Abuja Treaty is the blueprint and reference point for continental-level economic integration that was first established in 1991 to see to the creation of an African Economic Community (AEC). The Treaty acknowledges that, the African continent, as a unified unit of countries, wields immense power in the international system, in terms of trade and political influence, and thus it seeks to bring to fruition a highly integrated Africa. This study strives to evaluate the progress made on the implementation of the Treaty Establishing the African Economic Community (AEC) by comparing two regional blocs, the Economic Community of Central African States (ECCAS) and the Economic Community of West African States (ECOWAS), which serve as 2 of 8 building blocks for the realisation of the AEC. Accordingly, the research method used was qualitative and employed a purposive sampling method that draws on the selection of experts in the field of regional integration to shape the outcome of the study. The research findings include the fact that regional integration, on the continent, has progressed positively although it manifests slowly. Additionally, it found that both the ECOWAS and the ECCAS have progressed in terms of the implementation of the stages of the Abuja Treaty, although the former surpasses the latter in this regard. Yet, in spite of their progress, both RECs have faced challenges unique to their regions. ECOWAS for instance faces the problem of inability to completely enforce protocols on free movement of persons. The lack of national implementation of free movement legislation creates avenues for its ineffectiveness. Border checks are commonplace and there is very little standardization of official forms. ECCAS on the other hand faces a problem of overlapping goals and ideas with CEMAC as well as the failure of member states to carry out agreed decisions within their states due to issues such as conflict and instability in the region. On a whole, the study refutes the common idea that the Abuja Treaty has not been implemented at all but only sees its implementation as slow-paced.

The models of attribution in the establishment of corporate liability revisited - Heese, Francisca Alida (Stellenbosch University, 2019)
The separate legal personality of a company is one of the cornerstones of modern corporate law. Nevertheless, due to the artificial nature of a company it has no inherent moral blameworthiness necessary to impose corporate liability. With a rise in corporate wrongdoing, there is a need to hold companies liable. Therefore, certain models of attribution have developed whereby the conduct and will of a corporate actor can be imputed to the company to establish corporate liability. Especially in the realm of corporate criminal liability, these models of attribution have played a pivotal role to establish corporate wrongdoing. The two broad theories underlying the models of attribution are the fiction and realist theories respectively. The directing minds doctrine or identification doctrine and the vicarious liability model are traditionally associated with the fiction theory, which is rooted in the abstract nature of a company. Whether the traditional models of attribution are suited for complex modern organisational structures, is explored in this thesis, whilst a more functional and realistic approach to corporate liability is proposed. Often the question of “what is a corporation” has overshadowed the determination of corporate liability, thus a more contextual analysis based on law and economics is proposed to ensure corporate liability. The development of the rules of attribution through case law illustrate the importance of a purposive approach to establishing corporate liability. Furthermore, the underlying relationship between the rules of attribution and the rules of agency indicate that the interests of risk-bearers and managers are not always aligned and should be redressed. Moreover, a realist approach as opposed to the fictional approach to attribution has been developed in English and Australian law. This approach focuses on the overarching corporate culture and identity when determining corporate fault, instead of individual corporate actors. These regulatory frameworks provide an alternative approach to the current South African model, which is based on the fiction theory. Lastly, the economic considerations, such as the separation of ownership and control and the agency problem, are evaluated to determine whether the current models of attribution create an economically efficient outcome or an unsustainable a risk-taking environment.
Keywords: Corporate culture; Corporate liability; Corporation law

Choice of law in International Commercial contracts in the BRICS countries - Agbeko, Fafa Delight (University of Johannesburg, 2019)
Please refer to full text to view abstract. LL.M. (International Commercial Law)

Rethinking international employment contracts in the wake of the Fourth Industrial Revolution - Antwi-Larbi, Nana Amobea (University of Johannesburg, 2019)
Please refer to full text to view abstract. LL.M. (International Commercial Law)

Choice of forum in International Commercial Contracts : a comparison of the position in Ghana and under the Brussels IBIS regulation - Asante-Aboagye, Benedicta (University of Johannesburg, 2019)
Please refer to full text to view abstract. LL.M. (International Commercial Law)
Keywords: Belgium; Border trade; Conflict of laws; Ghana; International commercial contracts; Litigation

The treatment and recognition of company groups in South African corporate law - Diale-Ali, Regomoditswe Ursula (University of Johannesburg, 2019)
Abstract : Please refer to full text to view abstract. LL.M. (Commercial Law)

A critical appraisal of call centre contracts for insurance - Dladla, Mbongeni George (University of Johannesburg, 2019)
Abstract : Please refer to full text to view abstract. LL.M. (Commercial Law)

The release of liability of a surety during business rescue proceedings - Dubula, Mcebisi (University of KwaZulu-Natal, 2019)
Chapter 6 of the companies Act has attempted to resolve problems created by the ineffectiveness of judicial management which has failed to provide suitable alternative to the liquidation. The process of business rescue proceedings has made some impact on the liability of sureties in so far as it relates to creditors. Moratorium has been imposed once the business rescue proceedings commences and therefore the principal debtors are protected against any legal action unless the court or business rescue practitioner has consented thereto. The question is what is the impact of the business rescue proceedings on the rights of creditors against the sureties of the company under business rescue proceedings and what is the judicial position in so far as it relates to liabilities of sureties during business rescue proceedings, finally what is the position of comparative law in respect of other foreign Jurisprudence terms of business rescue proceedings and the liability of sureties. The South African Companies Act does not regulate the situation of creditor’s rights against sureties of a financially distressed Company. In terms of American law, the situation is different. Creditor’s rights against non-debtors (including sureties) is regulated by Bankruptcy Codes. In terms of bankruptcy codes, the discharge of a debtor does not affect the liability of the nondebtors or other entities. There are divergent views in terms of South African Court decisions in respect of liability of sureties. Some Judges believe that the commencement of business rescue proceedings does not affect the liability of sureties and others are of the view that the beginning of business rescue proceedings releases sureties from their obligations towards creditors unless business rescue plan or deed of suretyship provides otherwise. It is therefore recommended that our legislature introduces some new sections into the companies act. One Section should be similar to section 524(e) of the bankruptcy codes which expressly states that a discharge granted to the principal debtor does not affect the liability of sureties towards creditors. Another section should be similar to section 105(a), which provide courts with powers to make any order to realize the objectives of the companies act. This to avoid conflicting courts decisions on this issue.
Keywords: Bankruptcy; Creditors' rights; Insolvency; Liability of sureties; Reorganisation process; Suretyship

The role of the Hague principles on choice of law in international commercial contracts in Japanese private international law - Geraghty, Brandon Brian (University of Johannesburg, 2019)
Please refer to full text to view abstract LL.M. (International Commercial Law)
Keywords: Conflict of laws; Contracts (International law); Japan

A comparative analysis of mergers and acquisitions in South Africa, Botswana and Kenya : how can we achieve successful integration in Africa? - Gumede, Nomfundo Pretty (University of KwaZulu-Natal, 2019)
No abstract available.
Keywords: Acquisitions; Amalgamation; Bots; Business; Corporate mergers; Integration; Kenya; Mergers; South Africa

The contractual landscape and the protection of consumers in online auction contracts - Khan, Haleema (University of Johannesburg, 2019)
Please refer to full text to view abstract. LL.M. (Commercial Law)

Aquilian liability : the best remedy against delinquent company directors - Kharametsane, Godirilwe (University of Johannesburg, 2019)
Abstract : Please refer to full text to view abstract. LL.M. (Commercial Law)

An analysis of reinstatement as a primary remedy for unfair dismissal of employees in South African Labour Law - Mampholo, Yvonne Mokhubane (University of Johannesburg, 2019)
Please refer to full text to view abstract. LL.M. (Commercial Law)

Intermediaries and advisors' duties to disclose onerous clauses to prospective policyholders - Matshitse, Collen Kgaolo Stephen (University of Johannesburg, 2019)
Please refer to full text to view abstract. LL.M. (Commercial Law)
Keywords: Commercial law; Insurance law

The recovery of cultural property in international law: collaborative settlements of disputes - Mauro, Benedetta (LUISS Guido Carli, 2019)

An investigation into the effectiveness of trade unions in advancing the cause of workers during strikes in the face of an emerging culture of violence and criminality - Mfusi, Pearl Dawn Arnold (University of KwaZulu-Natal, 2019)
No abstract available.
Keywords: Labour protests; Liability; Strikes; Trade unions; Violent protests; Violent strikes; Workers

Towards development-centred trade relations: a study of South Africa and the USA trade relations with particular focus on the African Growth and Opportunity Act (AGOA) - Mkhwanazi, Nhlakanipho (University of KwaZulu-Natal, 2019)
With trade taking place continuously on a daily basis, its often-reported success gives the impression that all participants involved are to a certain extent somewhat successful too. This dissertation draws attention to the discrepancies that have often gone unnoticed throughout the decades and the effects that have arisen as a result. South Africa’s (SA) and the United States of America’s (US) trade relationship through the African Growth and Opportunity Act (AGOA) is the focus of this study, with this relationship being analysed from as far back as history has been recorded to the modern day. Least developed countries (LDCs) are an integral part of this study because most trade-related activities involve them, and they contain most of the world’s natural resources, but most importantly they also make up a large portion of the world’s population. It's baffling to see that where these factors are present, there's also inequality. Seemingly, there are efforts that deal specifically with the challenges faced by developing countries, but what is concerning is these solutions are formulated by developed countries which created them and continue to perpetuate them. The approach adopted was mostly that of contrasting events that have involved trade over the decades and a discussion of how these events have shaped international, political and trade relations, that is, the existing status quo. Examples include the two World Wars; oppressive regimes such as apartheid; and the formation of global institutions ranging from the International Trade Organization (ITO) to the General Agreement on Tariffs and Trade (GATT), and the World Trade Organization (WTO). The first three chapters contain an introduction, a background focus on development and the history of relations between South Africa and the United States of America. The last two chapters contain a discussion on AGOA as well as findings and recommendations that can be implemented to assist with this issue. What this dissertation was aiming to establish was the perpetual involvement of developed countries in the affairs of developing countries. This is illustrated through the renegotiation of the AGOA in 2015, where SA had to accept ultimatums set for it by the US. This dissertation further shows that such tactics are nothing new when the US is involved, as is evidenced by its involvement in major global events that have shaped the course of history. This approach is not only harmful but also stagnates development, as developing countries must adhere to agreements that sometimes are not to their benefit. The findings indicate a contradictory pattern: when solutions to challenges faced by developing countries are presented, they translate instead into a further stronghold over developing countries because of past atrocities such as colonisation and apartheid. What appears throughout the dissertation are the ever-present structures that are intended to perform functions supposed to be for the improved good of developing countries, but which result in those countries facing never-ending challenges, some of which are self-inflicted through alliances such as the AGOA with developed countries.
Keywords: AGOA; African Growth and Opportunity Act; Developing countries; Dumping; GATT; General Agreement on Tariffs and Trade; Trade relations; WTO; World Trade Organization

Price reduction as a remedy for breach of contract by the seller under the CISG and English law - Mukuna, Nomator (University of Johannesburg, 2019)
Please refer to full text to view abstract. LL.M. (Commercial Law)

The interruption of liquidation by business rescue application: a lacuna in the Companies Act - Ntingane, Neo Samantha (University of Johannesburg, 2019)
Abstract : Please refer to full text to view abstract. LL.M. (Commercial Law)

The rights of illegal workers not to be unfairly dismissed, with emphasis on illegal immigrants and sex workers - Ntshalintshali, Phindile Ziningi Glenn (University of KwaZulu-Natal, 2019)
Illegal workers have been and continue to be the most vulnerable category of employees in the labour market, the reason for this is the invalidity of their employment contract due to illegality. For the longest time, the Labour Relations Act (hereinafter the LRA) has not been able to afford these workers protection because they did not fall within the ambit of the legal definition of ‘employee’ and the Act only recognises employees as holders of the rights provided for under the LRA. As a result of the Act not being able to protect these workers, they have become victims of exploitation and vicious abuse in the hands of their employers, making them vulnerable in their employment relationship. The law concerning illegal workers has since changed. Courts have found that these workers are in fact employees for the purposes of the LRA, and that, for an employment relationship to exist there need not be a valid employment contract in existence. An employment relationship may take various forms and the goal that the Labour Relations Act seeks to achieve is to protect those employees who find themselves vulnerable as a result of the illegality of their employment contract. It has also been argued that the law aims mostly at penalising the employer rather than the employee who is economically and socially weaker than the employer, therefore, courts have found that the Labour Relations Act should be interpreted in a manner that is consistent with the Constitution of the Republic of South Africa (hereinafter the Constitution) which requires a wider interpretation of who may be afforded the right to fair labour practices.
Keywords: Illegal workers; Immigrants; Sex Workers; Unfair dismissal

The rights and duties of parties to liability insurance contracts at claim stage - Ntuli, Bonginkosi (University of Johannesburg, 2019)
Please refer to full text to view abstract. LL.M. (Commercial Law)
Keywords: Insurance claims; Insurance policies

Business rescue: a delay tactic for liquidation? - Nxumalo, Misiwe Mpilenhle (University of KwaZulu-Natal, 2019)
No abstract provided.
Keywords: Business rescue; Company creditors; Company law; Liquidation; Shareholders

The possible impact of the Hague Convention on the recognition and enforcement of foreign judgments in civil or commercial matters on private international law in common-law West Africa - Okorley, Solomon (University of Johannesburg, 2019)
Please refer to full text to view abstract. LL.M. (International Commercial Law)

The position of a director in South African Law : is it worth the risk - Raselo, Moeketsi Thebe (University of Johannesburg, 2019)
Please refer to full text to view abstract. LL.M. (Commercial Law)

Exemption clauses : contractual exclusion of delictual damages - Sande, Janet (University of Johannesburg, 2019)
Please refer to full text to view abstract. LL.M. (Commercial Law)

Unification of international sales law in the SADC region : the role and significance of the CISG - Simelane, Mbalenhle Pearl (University of Johannesburg, 2019)
The United Nations Commission on International Trade Law (UNCITRAL) is one of the most prominent legal bodies in international commerce. In 1980, the final draft of the United Nations Convention on Contracts for the International Sale of Goods (CISG or the Convention) was approved by the United Nations (UN) General Assembly and came into operation on 1 January 1988. Generally, the diversity of laws is an impediment to international and regional trade. Traders are discouraged from entering into international sales contracts due to the dissimilarities of legal systems. However, the CISG seeks to unify laws relating to the international sale of goods, whilst codifying the existing rules of international trade. The main objectives of the Southern African Development Community (SADC) are to achieve development and economic growth through regional integration.1 The legal integration and unification of sales law has a significant role to play in regional integration. Hence, SADC would do away with difficulties that affect interregional and intra-regional trade by impeding economic growth by making use of widely accepted trade laws, such as the Convention. International trade promotes both economic development and social upliftment. Moreover, democracy, political stability and human rights must be respected to foster sustainable economic growth and development in Southern Africa. 2 With advantages such as accessibility, flexibility, indorsing party autonomy, simplicity, and uniform interpretation, the paper revisits the call for the unification of laws on the sale of goods in SADC and considers the role and significance of the CISG in the region. LL.M. (Commercial Law)
Keywords: Commercial law; International economic integration; International trade Law; International unification

An appraisal of the implementation of the retail distribution review's recommendations - Wilkins, Chanel (University of Johannesburg, 2019)
Please refer to full text to view abstract. LL.M. (Commercial Law)

Determining the proper law of an International Funds Transfer - Yeboah, Abena Takyiwa (University of Johannesburg, 2019)
There are many ways of making payments. One of the available options for parties to international commercial transactions is international funds transfers. These transfers occur across borders and so, raise conflict of law issues. There are some laws known internationally that regulate international funds transfers. These laws include the UNCITRAL Model Law on International Credit Transfers (no country has ratified it), article 4A of the Uniform Commercial Code and the Rome I Regulation. There are diverse ways in determining which law applies to an international funds transfer. This is done either by assessing the transaction as a single transfer or as a set of linked transactions. In African countries like Ghana and South Africa, there is a gap in the approach of the law in addressing the conflict of laws issues regarding international funds transfers. This dissertation addresses the gap in these legal regimes using the present private international law as a guide. Additionally, the present legislation and legal jurisprudence are analysed, and suggestions are given as to its improvement. This author also advocates for a legislation that adequately addresses the issues raised by transnational funds transfers in these countries. Conclusively, this will promote a predictable approach in determining the applicable law in transnational funds transfers.
Keywords: Fund transfer; Transfert de fonds; Transfert international

The role of the SADC Protocol on Trade in Services in regional integration - Swanepoel, L. B. (North-West University, 2018)
Trade in Services can be described as a transaction between a supplier and a consumer without any physical movement of goods across international borders. This, in itself, presents major economic growth possibilities in both regional and multilateral terms. Regional trade agreements, if drafted to suit the specific region's strengths, can promote Trade in Services and establish regional integration. The fact that Trade in Services and regional integration, throughout the Southern African Development Community (SADC) specifically, is moving forward at such a slow pace is due to the lack of political ambition and policy makers failing to emphasise the establishment of trade specific regulatory coherence among member states. Given policy’s impact on Trade in Services, regional trade agreements must be designed to address new and emerging issues that, not only haven't been taken up in previous trade agreements, but which is also region specific and focused enough to build on new standards found in other new trade agreements that will boost regional integration. SADC countries are still in process of establishing a regional services market and, as it currently stands, major development possibilities still exist. This study compares the Trans-Pacific Partnership (TPP) with SADC’s Protocol on Trade in Services (PTIS), with the goal to determine the principles that are necessary to establish a regional market for the integration of Trade in Services. It was found that the PTIS lacks such principles and that integration of services throughout the SADC region is highly unlikely if set forth in its current direction. The finding was that the establishment of regional integration of Trade in Services throughout SADC will have to start with regulatory coherence among its members.
Boloka Institutional Repository https://repository.nwu.ac.za/handle/10394/31341
Keywords: Modes of trade; Regional integration; Regulatory coherence; Trade in Services

Trade Openness and Financial Development in Sub Saharan Africa: The Role of Institutional Quality - Abeka, Mac Junior (University of Cape Coast, 2018)
The financial development of many Sub-Saharan African countries over the years has not been able to match up with other regions like the Middle East and North Africa, East Asia and Pacific, and Europe and central Asia (IMF, 2016). Trade openness has been argued in several empirical literature as a factor that could spur up the level of financial development, although the high levels of trade openness in Sub-Saharan Africa is not contributing much to the desired levels of financial development in Sub-Saharan Africa. However, there is an indication in literature that trade openness will be more relevant to financial development of economies that have a strong institutional quality. Thus, by using system General Method of Moment estimation technique, this study examined how institutional quality moderates the relationship between trade openness and financial development of Sub-Saharan African economies. The study found that institutional quality enhances the effect of trade openness on financial development of Sub-Saharan African economies. It is therefore recommended that, Sub-Saharan African economies should put in measures to strength their institutional quality so that the high levels of trade openness will better enhance financial development. Specifically, trade openness can better enhance financial development by improving government effectiveness, reducing corruption, enhancing regulatory quality, abiding by the rule of law, and allowing voice and accountability. As an extra benefit, the improvements in institutional quality on their own too will yield positive impact on financial development.
http://ir.ucc.edu.gh/jspui/handle/123456789/4084

Cross border merger and shareholder's rights - Severino, Francesco (LUISS Guido Carli, 2018)
Historical context. Scope of application of cross border merger. A comparison of class rights with minority protection in cross border merger. The transposition of the cross border merger in the German law for an implementation.

An analysis of the effects of tax policy and tax abuse on the fulfilment of human rights in developing countries : the case of Zambia - Chigubu, Salome (University of Johannesburg, 2018)
Keywords: Droit fiscal; Pays en voie de développement; Politique fiscale; Tax; Zambie

The position of assets vested in a sham trust - Diedericks, C. A. (North-West University, 2018)
The concept of a sham trust has changed over the years. Presently it is defined as a perceived entity that is not entirely what it portrays to be. In addition, a sham is therefore regarded as invalid with a deceiving nature. A sham trust has the consequence that all the benefits and protection of assets are destroyed, seeing that no trust actually came into existence. Considering the above, for the purpose of the present study, only an inter vivos trust was evaluated and discussed in detail. The law of contract is considered to be the foundation of the principles for an inter vivos trust. Therefore, the law of contracts can be applied to solve problems presented by trusts. During the course of the present research, it became evident: in instances where a trust is declared a sham, the consequence is that the trust will be deemed void. There are instances where a sale agreement has been concluded prior to the discovery of the true nature of the trust, namely it being a sham. This raises the question on the legal position of assets vested in a sham trust. A further question arises about the consequences and whether the courts should set a guideline for such instances. From the findings it is evident that such a guideline is necessary. This would enable courts to determine the consequences of assets vested in a sham trust. There are various possibilities regarding consequences for assets vested in a sham trust. To determine the applicable consequence, the court should deal with each case individually based on the facts of that particular circumstances. This consequence could either entail that the assets should fall within the founder’s personal estate, or whether the concluded sale agreement should be deemed void. It is evident that the courts struggled with the distinction between a sham and alter ego trust, however, the case law referred to below gives more clarity in this regard. A proper formulation of the aspects of sham and alter ego trusts was provided in the cases of Van Zyl v Kaye1 and Van der Merwe v Hydraulics.2 The formulation of the two aspects in the above-mentioned cases was confirmed in the Supreme Court of Appeal judgement in the case of WT v KT.3 In the Khabola v Ralitabo,4 the court dealt with the typical example of the sham trust. In brief, the fact of the case were, that the parties had the intention to establish a partnership that was simulated to be a trust.
Boloka Institutional Repository https://repository.nwu.ac.za/handle/10394/31321
Keywords: Assets; Contract of sale; Intention; Law of contract; Legal position; Sham trust; Snook test; inter vivos trust

A comparative analysis of constructive dismissal in South Africa and within other international jurisdictions - Kader, Riaz (University of KwaZulu-Natal, 2018)
Abstract available in PDF.
Keywords: Constructive dismissal; Employee termination; Employees; Employers; Employment relationship; Termination of employment

Choice of law in international commercial contracts : a comparative study of Private International Law in Ghana and South Africa - Kwame, Essah (University of Johannesburg, 2018)

A comparative legal perspective on the impact of good or bad faith on the independence of documentary credits and demand guarantees - Lupton, Cayle Selwyn (University of Johannesburg, 2018)
Abstract : Please refer to full text to view abstract. LL.M. (Commercial Law)

Modification of choice of law in the BRICS countries : the role of Article 2(3) of the Hague Principles on choice of law in international commercial contracts - Ndlovu, Docus Sanele (University of Johannesburg, 2018)
Each member state of the BRICS countries is different about the modalities and limitations of party autonomy in their field of Private International law. The principle of party autonomy allows parties to choose the law applicable to their contract and is meant to respect the choice of contracting parties. Since laws are not absolute, they need to change to the needs of a changing society. This can generate a problem in instances where contracting parties have already chosen a choice of law to govern their contract. The question is then whether the governing law of a contract that was previously chosen by the parties can be changed after that contract has been concluded. The scope of party autonomy extends to permitting parties to modify their chosen law in instances where it is necessary to do so, subject to limitations of a specific legal system and principles of conflict of laws. However, the legal rules of each BRICS countries differ in permitting parties to modify the chosen law. This minor dissertation analyses whether the principle of party autonomy is recognised in each member state of the BRICS countries and whether it extends to allow for modification of choice of law. It further asserts that the BRICS countries could plausibly refer to the rules and recommendations of Article 2(3) of the Hague Principles on Choice of Law in International Commercial Contracts to advance the wide acceptance of modification of choice of law. LL.M. (International Commercial Law)

The directors’ fiduciary duty to act in the best interests of the company: the possible developments of common law by statute and how they affect human rights - Nomadwayi, Bakhulule (University of KwaZulu-Natal, 2018)
This research traces the developments of the directors’ fiduciary duty to act in the best interests of the company and looks at how these developments affect human rights and interests of stakeholders. The main focus of the study is on the human rights impact of this duty. Initially, this duty was only regulated in terms of common law which proved to be problematic. The problem with common law lies within the definition of ‘best interests of the company’, which not only exclude the interests of other stakeholders but also has the potential to bring about violation of human rights, particularly the rights to equality, dignity and fair labour practice. At common law best interests of the company means interests of the company itself and its shareholders. The common law only protects the company and its shareholders, while excluding the rights and interests of stakeholders. The common law duty to in the best interests of the company is not in line with our contemporary law because it ignores human rights. The neglect of human rights by this duty renders it inconsistent with the values contained in the Constitution. Furthermore, the exclusion of stakeholders’ rights by this duty cannot be justified because stakeholders play an important part in safeguarding the stability and continued existence of the companies. The fiduciary duty to act in company’s best interests is now contained in the Companies Act of 2008. Inclusion of this duty in the Act enables our courts to interpret it in a manner that protects human rights and which takes into account interests of other stakeholders. Section 7 (a) of the Act provides that among other goals of the Act is the promotion of compliance with the Bill of Rights when applying the company law. The impact of section 7 is that it imposes an indirect duty on directors to consider the human rights impact of their decisions. Section 158 of the Act enables the courts to “develop common law as it is necessary to improve the realisation and enjoyment of rights established by the Companies Act of 2008.” Given this recognition of the Bill of Rights by the Companies Act, it’s of vital importance that our courts should interpret and apply the duty to act in the best interests of the company in manner that is consistent with the Constitution. Directors are now obliged to pay attention to the human rights impact of their decisions.
Keywords: Best interests of the company; CSR; Corporate Social Responsibility; Fiduciary duty

Reckless and fraudulent trading by a company and the business judgment rule as a defence for directors - Peter, Lunga Cosmo (University of KwaZulu-Natal, 2018)
Abstract available in pdf.
Keywords: Business judgment rule; Company directors; Corporate governance; Fiduciary duties; Fraudulent trading; Good faith; Personal liability

Analysing and comparing the impact of misrepresentation and non-disclosure on the validity of a contract: similarities, differences and remedies - Ramphal, Kayra (University of KwaZulu-Natal, 2018)
This dissertation explores the concepts of non-disclosure and misrepresentation in South African law. The principal focus surrounds the effect non-disclosure as a form of misrepresentation has on the liability of contracting parties. In order to explore this effectively, the study explores the concept of duty of disclosure, and whether such a duty exists in South African law. Instances when a duty to disclose arises are explained, such as positive steps taken to conceal facts, the seller having sole knowledge of the material fact, an omission or misleading language, and a change in circumstances. Similarly to the English law duty of disclosure in relation to information in contracts uberrimae fidei, the similar South African law concept in insurance or agency contracts known as ‘utmost good faith’, is discussed and explored. The study determines whether such a concept should be a mandatory requirement in pre-contractual negotiations. Additionally, this study explores the various avenues of relief that are available to those who have fallen victim to misrepresentation. This results in an analysis of the effectiveness and success of the current traditional methods of claiming and quantifying damages that are adopted by South African legislature and the judiciary. The discussion then explores the proposed alternate method which aims to combine a claim into one of delict and that of contractual liability, or on the other hand institute a claim solely based on contractual liability. Lastly, this study explores the effect the Consumer Protection Act 68 of 2008 has had on contractual agreements, remedies and penalties, and how this ground-breaking legislation has altered the approach previously adopted by the common law and whether it has done enough to protect consumers.
Keywords: Contracting parties; Contracts; Duty to disclose; Liability; Misrepresentation; Non-disclosure

The interconnection between express choice of forum and tacit choice of law. A comparative analysis between common-law and civil-law jurisdictions - Roux, Keegan (University of Johannesburg, 2018)
Keywords: Commercial law; Conflict of laws; Contracts (International law)

The link between reckless credit and emolument attachment orders - Singh, Nishtha (University of KwaZulu-Natal, 2018)
South Africa has experienced significant levels of reckless credit thus leading to over-indebtedness of consumers. Furthermore, research conducted in 2008 and 2013 by the University of Pretoria indicated that there were abuses prevalent in emolument attachment orders (EAOs). An interesting aspect of the research was that credit providers were particularly interested in employed consumers, as their wages or salaries were deemed to be a form of security. The aim of this dissertation is to examine the link between reckless credit and EAOs. The main research problem revolves around the fact that credit providers do not conduct thorough pre-agreement assessments and have a tendency to subscribe to the tick box approach to compliance. Moreover, these pre-agreement assessments do not make provision for the inclusion of external market factors, which is essential to safeguard consumers against economic events. This dissertation argues that, at the point when reckless credit is granted, it is inevitable that default will occur thus leading to the culmination of an EAO. In this regard, the case of University of Stellenbosch Legal Aid Clinic and Others v Minister of Justice and Correctional Services and Others; Association of Debt Recovery Agents NPC v University of Stellenbosch Legal Aid Clinic and Others; Mavava Trading 279 (Pty) Ltd and Others v University of Stellenbosch Legal Aid Clinic and Others (CCT127/15) [2016] ZACC 32 is important. The judgement illustrates how vulnerable consumers fell prey to unscrupulous credit providers who then took advantage of their salaries. An important aspect about the judgement was that section 65J of the Magistrates Court Act has now been amended through a joint interpretative mechanism of severance and reading in. The Constitutional Court’s order now requires judicial supervision in the EAO process, whereby a magistrate issues the EAO. This dissertation examines the effect of this and how EAOs are currently regulated. It also discusses whether judicial supervision is the solution to ameliorating the law on EAOs. Qualitative research methods were utilised such as legislation, case law, textbooks and journal articles. While there are no statistics to prove the link, anecdotal evidence proves the link between reckless credit and EAOs.
Keywords: Credit market; Emolument Attachment Orders; Protection of Personal Information Act; Reckless Credit

Restraint of trade clauses: does the enforcement thereof promote anti-competitive behaviour in South African law? - Sithole, Mthokozisi Wesley Nhlakanipho (University of KwaZulu-Natal, 2018)
No abstract available.
Keywords: Anti-competitive behaviour; Business agreements; Competencia; Competition law; Employment agreements; Restraint of trade; Trade clause

A discussion of the success and failures of business rescue as a remedy for ailing companies - Sobantu, Vuyo (University of KwaZulu-Natal, 2018)
Companies are constantly facing risks, including financial constraints, which may contribute to companies being unable to trade in the manner desired. Unfortunately, companies that find themselves in this predicament have, in reality, been without a remedy from as early as statutory provisions regulating company law were promulgated in 1926. Judicial management, as a remedy, is notorious for being an outright failure, but the current Companies Act 71 of 2008 introduced the remedy of business rescue for financially distressed companies. The scrutiny and spotlight on the new remedy turns on whether it can be truly accessible for the companies in question and what significant changes it has made to favour financially distressed companies. This mini dissertation will aim to discuss whether the remedy of business rescue has been a success or failure.
Keywords: Ailing companies; Business rescue; Companies Act 61 of 1973; Companies Act 71 of 2008; Judicial management; South African company law; Winding up

A critical analysis on simulated transactions - Tshabalala, Alwanduxolo Thembalihle (University of KwaZulu-Natal, 2018)
No abstract provided.
Keywords: Simulated transactions; Tax avoidance; Tax evasion; Taxation

The effects of business rescue on the companies’ stakeholders : a comparative analysis between business rescue and judicial management - Xaba, Ntombikhona Thandeka (University of KwaZulu-Natal, 2018)
Upon the recognition that the implementation of the judicial management process would not be the success that it was anticipated it would be, it became apparent that there was need for a system of corporate rescue appropriate to the needs of a modern South African economy. The legislature then introduced a new business rescue regime when the Companies Act 71 of 20082 (the Act) came into effect in the South African law. This new Act remarkably changed corporate law. One of the central features of the Act is the introduction of business rescue- a procedure which provides for the rehabilitation of financially distressed companies in a manner that seeks to balance the rights of all stakeholders. These provisions are said to be the appropriate method for modern South African economy and they differently affect the stakeholders of a company. This thesis will be discussing the different rights given to affected persons in the new Companies Act and examine how the provisions of business rescue affect different stakeholders of the company and compare such effects with those experienced under judicial management, specifically in light of the improvements of the positions of the stakeholders. Although the new business rescue is a remarkable improvement from the old judicial management system, there is still room for improvement.
Keywords: Business rescue; Companies Act 71 of 2008; Company stakeholders; Judicial management; South African company law

A critical discussion of the directors’ duties and business judgement rule - Zondi, Sphesihle Brilliant (University of KwaZulu-Natal, 2018)
No abstract available.
Keywords: Companies Act 71 of 2008; Directors; Judgement rule; South Africa

Treatment of corporate groups in insolvency under EU law - Sicignano, Luca (LUISS Guido Carli, 2017)
L’analisi svolta in questo lavoro ha ad oggetto le procedure adottabili in caso di fallimento, quando esse coinvolgono società costituite in gruppi di impresa. È una questione non recente che ha tuttavia avuto la sua consacrazione nel panorama internazionale solo negli ultimi anni. La grande crisi finanziaria del 2008 ha fatto sorgere la necessità di emanare nuove specifiche regole. Pertanto, l’obiettivo che questo lavoro si propone, è di analizzare tali regole, sia iure condito che iure condendo, per consentire al lettore di avere una panoramica chiara su come l’insolvenza di gruppo possa essere trattata.

Dissenting Opinions in International Commercial Arbitrations - Mohanty, Gautam (Central European University, 2017)
A dissenting opinion with reference to International Commercial Arbitrations elementarily denotes the expression of disagreement by an Arbitrator in relation to both the reasoning and the result of the award granted by the majority of the Tribunal. Though still at a nascent stage, the practice of delivering dissenting opinions is one which needs to be duly noted and taken into due consideration because of the incidental and collateral questions that it nurtures. Fundamentally, a dissenting opinion raises concerns related to the effect, the nature and the rectitude of such opinions. One such collateral question is the enforceability of such dissenting opinions and the repercussions that follow in the context of an arbitral award delivered by the majority. In addition to the above raised question, through this thesis the author will also address other questions such as whether the act of delivering a dissenting opinion is an indicator of the increased sense of maturity of arbitrators in international commercial arbitration? Whether the dissenting opinion possesses any precedential value to the arbitration cases arriving prospectively? and How do such opinions contribute to the development of arbitration jurisprudence. Moreover, through this thesis the author will also attempt from a comparative perspective to examine and make an incisive analysis of the governing rules of arbitration across various arbitration regimes such as ICSID, LCIA which already have a wellestablished arbitration jurisprudence.

An investigation into the relationship between the UNIDROIT Principles of International Commercial Contracts (UPICC) and the UN Convention on the International Sale of Goods (CISG) - Daniel, Jason (University of Johannesburg, 2017)
LL.M. (International Commercial Law) Please refer to full text to view abstract
Keywords: Commercial law; Conflict of laws; Contracts (International law); International Institute for the Unification of Private Law; UNIDROIT principles of international commercial contracts 2010; United Nations Convention on Contracts for the International Sale of Goods (1980 April 11)

Special and differential treatment provisions within the World Trade Organization : the pursuit of development for developing countries - Hiine, Karabo (University of KwaZulu-Natal, 2017)
Abstract not available.
Keywords: Differential Treatment Provisions; Multilateral system; Special Treatment Provisions; Trade liberalization; WTO; World Trade Organization

Alternative Dispute Resolution in Oil and Gas Contracts Law: An Analysis - Kareem, Kareem Kawa (Near East University, 2017)
The industry of oil and gas is not peculiar to question anymore, inferable from the global condition as well as its various dimensions. While trying to complete an agreement procedure, it would barely be clear to expect the thing that could happen in the emergence of a debate. Hazard moving and fragmented contracting lie at the heart of the organization relationship innate in the obtainment and financing of extensive scale undertakings, such as power plants, oil and gas pipelines, and condensed natural gas facilities. An examination of gas bonds gives exact proof of the hazard moving results of legally binding inadequacy. This thesis is a basic examination of the discipline we call the law of oil and gas. A number of the imperfections connected with this "specific" status. Jurisprudential with its "uncommon" status. Jurisprudential imperfections have created as courts leave from essential contract, property, or tort law in quest for natural resources ideas. The marvel isn’t restricted to natural resources law but instead can occur in any "law of" setting. This article delineates the issues connected with oil and gas law by dissecting legal ways to deal with perceiving and applying "inferred agreements" under the oil and gas rent. By contrasting the experience and results under the oil and gas lead to the result under an agreement law investigation, it is conceivable to assess whether a specific "oil and gas" govern is vital or prudent. In the past quarter-century, huge changes have happened in the ways legal advisors approach strife. There have been uncommon endeavors to create systems went for more proficient, not so much expensive, but rather more fulfilling determination of contention, including more broad and suitable utilization of intercession and other " alternative dispute resolution " (ADR) approaches. This review analyzes what is known and not considered about the development and effect of ADR in government and state courts, in the business division, and in work and shopper settings. The investigation inspects the relationship amongst ADR and court trial, additionally underlines the more extensive employments of and method of reasoning for intercession and different process decisions. This study concentrates on the oil and gas contract with question by ADR.

Recognition and enforcement of foreign judgments : proposals for OHADA - Kazadi, Nshingu (University of Johannesburg, 2017)
LL.M. (International Commercial Law) Please refer to full text to view abstract
University of Johannesburg Institutional Repository (UJ IR)

A critical analysis of the fiduciary duties of directors and evaluation of the development of these duties in terms of the common law and statutory law - Mdunge, Mzwendoda Smiso Patson (University of KwaZulu-Natal, 2017)
Corporate law is based on the premise that directors are fiduciaries of their companies. This is an unbending duty which has to be adhered to at all cost by individuals appointed as directors of a company. Previously the director’s duties were governed by the common law which often relied on the interpretation of the courts on a case by case basis. Therefore the courts would often arrive at different conclusions based on a similar set of facts. The advent of the 2008 Companies Act (Act 71 of 2008)1 brought about a major evolution in South African company law by partially codifying the fiduciary duties of the directors. Understanding fiduciary duties of a director is of significant importance in the modern democracy based on the fact that directors engage on the international spectrum. Company directors have discretionary power which may be abused if they are not familiar with the fiduciary duties. This study seeks to comprehend fully the fiduciary duties of a director of a company. These are the duty to act bona fide, the duty to act for a proper purpose, the duty to avoid conflicts of interest and the duty not to use a corporate opportunity and information for personal profit. This task will be undertaken both in terms of the common law as well as statute (Companies Act 2008 Act). The study will delineate the fundamental consequences of partial codification of these duties and set out the current legal position of the common law which operates in tandem with the statute. In addition, it will deal with whether the common law provisions are still applicable side by side with the statutes. The duties of a company director represent a subject that is not merely academic in nature, but one that is of vital importance in our ever changing commercial world. More and more people are appointed as company directors every day and often they do not know or understand the implications of what they have agreed to.
Keywords: Common law; Companies Act 71 of 2008; Corporate law; Duties of directors; Duty to act in good faith; Fiduciary duties

Contractual regulation : infusing the law of contract with constitutional values - Ndlebe, Zithulele Fikile (University of Johannesburg, 2017)
The Constitution of the Republic of South Africa is the supreme law in the land. Thus, all law is subject to the Constitution and this inevitably includes the law of contract. The South African law of contract has been inherited from common law, namely Roman–Dutch law and has been applicable in South Africa to date. The Constitution states that the common law should be developed when it is not in line with the provisions of the Constitution. The values underpinning the Constitution are human dignity equality and freedom and these values must therefore be reflected in contractual relations. The common law principle of pacta sunt servanda, which means that agreements must be kept, at times this principle yields unjust and unreasonable results. The strict adherence to pacta sunt servanda has led to difficulties. The unenforceability of these contract terms has been shown in reported case law to stem from standard term contracts, unequal bargaining power and from persons who contract out of necessity. This dissertation concludes that South African law of contract and the current legal treatment of balancing contract law with constitutional values is unsatisfactory. The Bill on the Control of Unreasonableness, Unconscionableness, or Oppressiveness in Contracts or Terms which was tabled in 1998 should be revised and legislated, so as to regulate contracts and infuse the law of contract with the constitutional values of human dignity, equality and freedom.

The impact of leadership styles on organizational performance - Nzimande, Sandile Jerome (University of KwaZulu-Natal, 2017)
Many contemporary private and public enterprises have been hit by scandals and underperformance which have been linked to organizational leadership. This study therefore sought to establish the impact of leadership styles on organizational performance. Leadership and organizational performance crises that have rocked institutions such as Eskom, the South African Broadcasting Corporation and the South African Airways, Steinhoff, Enron and others necessitated the study. The study focused on MBA year three students (class of 2017) at the University of KwaZulu-Natal. The assumption has been that since these are masters’ students, they have once been exposed to various leadership styles, some of them are leaders, all have studied leadership styles and therefore likely to understand how these styles impact on organizational performance. This is a quantitative study. The total population was 140 students of which a total of 100 were targeted. Simple random sampling was used. Most of the participants revealed that there is a significant link between leadership styles and organizational performance. They unanimously agreed that there is definitely a noteworthy relationship between leadership styles and the organizational performance. The respondents also revealed that transformational leadership style is the most complimentary leadership style to organizational performance followed by strategic and open leadership styles respectively. Participants agreed that toxic leadership style and autocratic leadership style are undermining the organizational performance. It is therefore recommended that organizations ensure continuous checks on leadership in order to ensure that available leadership can assist in the realization of organizational goals. In addition, it is also recommended for organizations to assess the "type" of a leader in terms of leadership styles before he/she is promoted to take leadership roles in the organization in order to make proper placements. This will allow the organization to assess whether that type of a leader is suitable for the organization. Future research is needed on how models can be developed on how to make proper placements to leadership levels/roles. Research should also focus on how leadership styles dovetail with other organizational efforts that are meant to boost organizational performance.
URI: https://researchspace.ukzn.ac.za/handle/10413/21460
Keywords: Leadership styles; Organizational performance; Private enterprises; Public enterprises

Strategies adopted by Commercial Banks in Kenya in Response to the Law Capping Interest Rates - Ragor, Rodgers Kiptoo (University of Nairobi, 2017)
The ability of an organization to adjust its operation in light of the evolving changes in their operating environment determines the sustainability of the business unit in both the short and long term. The objective of the study was to determine the response strategies adopted by Kenyan commercial banks in response to the interest capping laws. A descriptive cross-sectional design was used. The population of the study was 42 commercial banks operating in Kenya. Primary data was collected using a questionnaire that was both closed and open ended. Data was analysed using the descriptive statistics. The study found that banks have employed adaptation strategies through working with other partners in the banking sector to leverage their synergy and concentrate on areas that enhance competitive advantage. The research findings also reinforced the need for the banks to work together as a sector and attempt and change the laws that inhibit their operations through lobby groups in parliament and other forums. The study also show that there exists a link between firms‟ strategic activities and their strategic responses and therefore, bank managers should diversify their product range especially to the youth who are apt in using the mobile technology to access services and improve the bank level of efficiency and effectiveness in their operations. The study recommends that the commercial banks ought to conform to the regulations to attract customers while the Central Bank as a regulator should likewise be sensitive to the operating environment and should be flexible in setting the rules in order to attract investment and support the growth in the banking industry. The Interest capping law is still at its infancy stage in Kenya and thus there is room for further research as the full impact of the law is realized in the long term.

The compatability of the restatement second of the conflict of laws and South African private international law with Article 2(2) of the Hague Principles on Choice of Law in International Commercial Contracts - Seckel, Ashely Zwelinhle (University of Johannesburg, 2017)
Please refer to full text to view abstract. LL.M. (International Commercial Law)

State interference through domestic courts in international commercial arbitration - Badenhorst, Casper Hendrik Jacobus (University of Johannesburg, 2016)
Keywords: Arbitrage; Arbitragem; Arbitration; International and municipal law; International commercial arbitration

The Interface Between Competition Law and Intellectual Property Law in Kenya - Jerobon, Rotich Caroline (University of Nairobi, 2016)
The interaction between competition law and intellectual property law has often attracted divergent views from scholars and practitioners of each respective sphere of law. Whereas some argue that the two are in conflict with each other and cannot be reconciled. The aforementioned tension between competition law and intellectual property law has been traced to the objectives of each. On the one hand, intellectual property rights confer upon their owners an exclusive right to behave in a particular way while on the other hand competition law strives to keep markets open. Other scholars have argued that, in real sense and practice, the two are actually not in conflict but rather that they complement each other. The question then becomes, is there really an irreconcilable difference between the two areas of law? This paper seeks to establish how the two aspects of law interact and seeks to propose that there be created a balance to alleviate the perceived conflict between the two. This paper will identify the areas in which the balance can be struck. It will also seek to establish how the Kenyan legislative framework as well as the courts has dealt with the conflict. It will proceed from understanding the goals and objective of both intellectual property law and competition law. This will provide the backdrop against which the alleged conflict originates from. A comparative study with other developed jurisdictions will be undertaken so as to advise on the route that should be taken by Kenya on the interface and a conclusion drawn on how the two areas relate and recommendations drawn from the issues identified in the study made.
Keywords: Competencia; Competition law; Intellectual property

The resolution of jurisdictional conflicts under the common law and in the European Union - Mlambe, Richard Mike (University of Johannesburg, 2016)
The resolution of jurisdictional conflicts is one of the main functions of private international law. It provided rules to be applied when the courts of more than one country are seized of the same case in international litigation. In determining what that rule should be, regard must be had to the interest of all the relevant entities, namely, the parties to international cases and the courts dealing with such cases. The need to strike a balance is even more urgent in international commercial litigation where the outcome of the case normally has significant economic consequences. From this background, a study has been conducted of two major private international law regimes regarding their approaches to the resolution of jurisdictional conflicts, namely, the common‐law and the European Union (EU). This study is an inquiry into the suitability of each approach in the resolution of jurisdictional conflicts in international commercial cases. It is the view of the present author that each approach has advantages and disadvantages. The common‐law through the doctrine of forum non conveniens shows a greater ability to prevent forum shopping and to prevent injustices in specific cases. However, it is highly unpredictable. On the other hand, the EU approach through the lis pendens rule succeeds in ensuring predictability and certainty in the resolution of jurisdictional conflicts which is very crucial in international commercial litigation. However, its rigidity and inflexibility leads to the determination of international commercial cases by courts that are ill‐suited, thereby giving some room for forum shopping. It is therefore recommended that the two approaches should learn from each other so that their handling of international commercial cases is in line with the special nature of international commercial litigation. The common‐law approach should be made more predictable and the EU approach should allow the courts in the EU to determine which court is best suited to deal with an international commercial case.

The implications of Lagoon Beach Hotel (Pty) v Lehane 2016 (3) SA 143 (SCA) for the South African cross-border insolvency dispensation - Moolman, Shirande (University of Pretoria, 2016)
This mini-dissertation explores the implications of Lagoon Beach Hotel (Pty) Limited v Lehane 2016 (3) SA 143 (SCA) for the South African cross-border insolvency dispensation, as this case deals with the various problems that arise in cross-border insolvency. As a result of these problems and a certain amount of uncertainty when it comes to dealing with cross-border insolvency issues, many investors are reluctant to invest cross-border. This is due to the fact that multiple countries, each with their own laws concerning cross-border insolvency, are involved. Thankfully, the United Nations Commission on International Trade Law has provided a set of guidelines in this regard, namely the Model Law on Cross-Border Insolvency. Although South Africa has enacted the Cross-Border Insolvency Act 42 of 2000, and most of the provisions provided for in the Model law have been included in the legislation, the Act still remains inoperative. Throughout this dissertation the Lagoon Beach case will therefore be critically analysed. The analysis will start off with a discussion of the common law, as it is currently the legal position in South Africa. Thereafter a detailed analysis will be conducted of the various orders of court of the Lagoon Beach case and how the courts differed or agreed in their approach. Finally, the Lagoon Beach case will be discussed in light of the Act and the issues in the case will be solved hypothetically by applying the Act to the problems discussed throughout the dissertation.

The transfer of ownership of movables in the context of international contracts of sale with specific reference to reservation of title clauses : a comparative study - Neibecker, Nadine (University of Johannesburg, 2016)
Please refer to full text to view abstract LL.M. (International Commercial Law)

Designing justice: a critical analysis of intellectual property rights within the fashion industry - Parbhoo, Sade (University of KwaZulu-Natal, 2016)
Designers are those individuals within our society with a desire and drive to create. In general designers can be found in all facets of industry and good designers (and ultimately good designs) are the very backbone upon a successful business is built. Designers are required to marry practical knowledge with artistic ability and we are reliant on their skills and to turn abstract ideas into formal designs for everything from the groceries we purchase, the cars we drive and of course, the clothes we wear. Whilst there is no definitive delineation of what a fashion design is, generally fashion designs relate to the creation of designs that focus on clothing, apparel and accessories. The style and functionality of the end products rest firmly within particular time frames, economic and socio-cultural environments within which particular designers find themselves. Accordingly the fashion design industry is never one that stagnates but rather is one that is constantly evolving. In South Africa, the fashion industry is blossoming. As an emerging economy, it is important to create opportunities and not barriers for entry into particular sectors for emerging entrepreneurs. The entire fabric of the fashion industry has certainly changed over time and these changes have brought an increased focus on issues of copying and counterfeiting. It is the contention of some in the industry that there is a need for stricter protection of the actual design in and of itself. Using intellectual property rights as a means of protecting fashion designs is very fitting as every new design begins with an idea, which then evolves, though a process of creative engagement and application of skill and labour to become the final original end product. Designers seeking to protect their designs would need to consider the provisions of the Copyright Act, the Designs Act and the Trade Marks Act. These Acts may in some instances provide a means for protect the actual design incidentally, i.e. by protecting the designer‟s rights in relation to reputation and goodwill associated with the goods whilst in others may afford protection to the design itself. The focus of this research will be a discussion of the legal mechanisms available to fashion designers in South Africa for the protection of their designs using their intellectual property rights and an assessment of whether the fashion industry is in need a stronger intellectual property regime than the current one.
Keywords: Design protection; Fashion industry; Intellectual property; Ownership; Retail trade; South Africa

Formation of Contract for the International Sales of Goods - Saleem, Saman Othman (Near East University, 2016)
The Convention for the International Sale of Goods called the Vienna Conference 1980 is an astute international statute that regulates the sale of goods globally. It has been ratified by about 83 countries of the world and countries that have not ratified it have at a point or the other made reference to it. Major economic players apart from England have ratified and have their courts pronounce on the CISG. The Convention provides for the well known elements of contract and also allows for the usage of standard user terms, for example, general terms known or related to certain goods. It is imperial to state that there are also certain regional statutes that are similar to the CISG although with varying differences. It is important to also mention that the CISG also has its lacunae and defects such as allowance for exemption, contents and so on. The CISG has been pronounced upon by courts across the world and has been seen to be highly justiciable.
Keywords: CISG; Convention; English Law; Iraq; United Nations

Affected persons in business rescue proceedings : has a balance been struck? - Silangwe, Thandeka (University of KwaZulu-Natal, 2016)
Abstract not available.
Keywords: Buisness enterprises; Business failures; Corporate turnarounds; South Africa

An analysis of the impact of the sanitary and phytosanitary agreement on market access : case study on the SA/EU citrus dispute and AGOA dispute - Singh, Shikira (University of KwaZulu-Natal, 2016)
Abstract not available.
Keywords: AGOA; African Growth and Opportunity Act; Cooperation Agreement; Market access; Sanitary and Phytosanitary (SPS) Agreement; Trade Development; Trade barrier; WTO; World Trade Organization

The non-cooperative respondent in international arbitration proceedings : a comparative survey and evaluation of the leading arbitration rules - Venter, Johanlene (University of Johannesburg, 2016)
International arbitration has become accepted worldwide as the principal and, under certain circumstances the preferred method, of resolving international disputes between states, individuals, and corporations in almost every aspect of international trade, commerce, and investment. In general terms, it is expected that an international arbitration procedure is a much speedier method of dispute resolution than formal court proceedings. Although international arbitration holds many benefits for prospective users, there are some difficulties that may arise along the way. An increasingly frequent complaint concerns delays, particularly unconscionable delays and deliberate delaying tactics caused by the parties (i.e. claimant, respondent and/or the arbitrator) which frustrates the process. Arbitration derives from the consent between contracting parties. This implies that the contracting parties gave their consent that a dispute arising from the contract may be resolved by way of arbitration. This will also explain why default by any of the parties is prima facie inconsistent with the consensual nature of arbitration. It is suggested that default during international arbitration is most likely to occur and does not receive the same treatment as the equivalent in the context of formal state court proceedings. Essentially, the objective of this study is to articulate what the claimant can and should do during the arbitral process if and when the respondent is non-cooperative and obstructive in the arbitral process in an attempt to delay and/or destroy the procedure. This study also considers how tribunals should behave in order to promote fairness and the most efficient form of dispute resolution. The research method applied during this study is to conduct a comparative survey and evaluation of the leading arbitration rules available in order to establish what measures are put in place to overcome or mitigate the effects caused by the non-cooperative respondent.
Keywords: Commercial law; International commercial arbitration

The suitability of the CISG and OHADA for small and medium-sized enterprises engaging in international trade in West and Central Africa - Donfack, Narcisse Gaetan Zebaze (University of South Africa, 2015)
It is universally acknowledged that international trade and cooperation have become key drivers of SMEs. Indeed, the success of SMEs in the sales sector depends upon their capacity to conquer the foreign market and compete with larger companies. Many SMEs today, in particular those in Central and West Africa, are very much aware of this reality. However, because of differences between domestic laws and their maladjustment, many African SMEs still struggle to enter the international market and compete with larger companies. It is therefore obvious that any SMEs that want to succeed in international commerce today will be called upon to confront different regulations, whether domestic, regional or international, which are often shaped according to the realities and expectations of a particular environment. The challenge today is to regulate and harmonise these different legal systems, in order to render the law identical in numerous jurisdictions. This process of unifying the law internationally, in particular the law of sale, started in 1920 and culminated in 1988, with the implementation of the CISG. This Convention, which has become the primary law for international sales contracts, endeavours to deal with this problem of differences in law between states on a global scale, by attempting to achieve a synthesis between different legislations, such as civil law, common law, socialist law, and the law regarding industrialised and Third World countries. Even though the CISG appears to be a compromise between different legal systems, the fact remains that it is not yet applicable in many countries, especially those in Central and West Africa, which are mostly still ruled by domestic and regional law, namely the OHADA. The purpose of this study is to attempt to analyse and compare the OHADA’s Uniform Act Relating to Commercial Law to the CISG, in order to identify similarities and differences between the two, and to determine, with regard to the operating mode and structure of SMEs in West and Central Africa, which one of the two legislations is more appropriate.
Accepted: 2016-07-19T07:00:06Z
Keywords: CISG; Cameroon Civil Code; Cameroon contract law; Comparative law; Formation of a contract; Incoterms; International sales law; Internationalisation; OHADA law; Obligations of the buyer; Obligations of the seller; SMEs; Sales of goods; Termination of a contract

Passivity rule: a comparison between European Union, United States and China - Casamassima, Stefano (LUISS Guido Carli, 2015)
Passivity rule: origin and reasons. Adoption of the European directive 25/2004 and its provisions. The adoption of the European directive by major member states and passivity rule in USA and China. The economic implications of passivity rule. Possible future developments.

Choice of the UNIDROIT Principles of international commercial contracts - Meer, Tiana Van der (University of Johannesburg, 2015)
LL.M. (International Commercial Law) The principle of party autonomy is a fundamental characteristic of private international law. The contracting parties’ freedom of choice regarding the law governing their contract is one which optimises the fundamental principle of party autonomy. It is generally accepted that a choice of a governing law by the parties should be respected by adjudicating bodies such as domestic courts and arbitral tribunals. It would often benefit contracting parties to choose a neutral legal system so that there will be a “fair playing field” in case a dispute arises between them. However, some domestic legal systems and regional, supranational and international commercial instruments limit the choice of law to that of a recognised domestic legal system. Accordingly, choosing the UNIDROIT Principles on International Commercial Contracts as governing law will, in most cases, not be a viable option for the parties concerned. Such a limitation on the choice of a governing law does not promote the fundamental principle of party autonomy, which is characteristic of private international law. Parties to an international commercial contract should be able to choose a non-state system of law to govern their contract. The UNIDROIT Principles of International Commercial Contracts provide a comprehensive, complete and easily obtainable system of law compiled by legal experts in the various fields which form part of international commercial law. It follows a via media system of law with regards to Civil Law and Common Law legal systems. This paper will discuss the principle of party autonomy, as well as the possibility of a choice of non-state law, in particular the UNIDROIT Principles of International Commercial Contracts, as the law governing an international commercial contract. The choice of law will be discussed with reference to the position taken in domestic courts as well as that in international arbitration. To review the impact and success of the UNIDROIT Principles in the realm of international commercial contracting, various international commercial instruments will be discussed.

The potential impact of the Hague principles on choice of law in international commercial contracts in the BRICS countries - Reddi, Saranya (University of Johannesburg, 2015)
LL.M. (International Commercial Law) Please refer to full text to view abstract
Keywords: BRIC countries; Commercial law; Conflict of laws; Contracts (International law)

A comparison of Kenyan and South African law on security by means of movables - Koli, Natasha Mwende (University of South Africa, 2015)
This study compares the legal principles applicable in both South Africa and Kenya in the creation of security by means of movables. It identifies the forms of security that can be created in the two jurisdictions. The main focus will be on the creation, publicity, priority of security interest and enforcement of the said interests. The research will in addition establish the challenges (if any) that are encountered when creating security by means of movables in Kenya and identify practical solutions that can be adopted in order to improve the creation of security by means of movables in Kenya.
Accepted: 2015-10-16T08:35:59Z
Keywords: ACCESS TO FINANCE; Creation of security; Kenyan law; Lenders and security; Movable property; Secured transactions; Security; Security by means of movables; South African law

Cross border insolvency: new trends - Napolitano, Andrea (LUISS Guido Carli, 2015)
The EU regulation no. 1346/2000. The proposal for a modification of the regulation. New trends.

How to copy a song with impunity : a legal perspective on copyright infringement cases for musical works - Rogowski, Adrian (Stellenbosch University, 2015)
Music has, and continues to play, an important role in society. It is therefore natural that more music composers enter the scene to capitalize upon this role that music has in society. It is however becoming more common place for music composers to start copying each other, either directly or indirectly. Fortunately, copyright laws have been developed to further protect the rights enjoyed by copyright holders, such as music composers, and these laws essentially protect the composers from the unlawful reproduction of their original music. Copying is, to some degree, inevitable, therefore, the question asked by this paper is to what extent is someone entitled to ‘copy’ from another person without it amounting to copyright infringement. In determining if there is copyright infringement, two tests must be applied and satisfied, namely, the causal connection test, and the substantial similarity test. Causal connection is usually met by establishing whether the alleged infringer had access to the original work. The substantial similarity test is the focus of this paper. The courts rely on this test to determine if that part which was reproduced from the original work is of substance i.e. if it is a part of the work which attributes uniqueness and quality to the original song. Of course, this test is notoriously difficult to understand and apply, hence the need for this paper to address the question on when there is substantial similarity in two works. This paper is of benefit to academics, authors (musicians) and lawyers, as not only is the substantial similarity test discussed from a theoretical point of view, but the question of when something is substantially similar is answered from a pragmatic point of view. It is hoped that this paper is used as a guideline in understanding and applying the substantial similarity test in music copyright infringement cases.
Keywords: Copyright; Copyright infringement; Music; Musical compositions

Reconsidering Distributions: A Critical Analysis of the Regulation of Distributions to Shareholders in the Companies Act of 2008, with Special Reference to the Solvency and Liquidity Requirement - Van der Merwe, Constant Pieter (Stellenbosch University, 2015)
The Companies Act 71 of 2008 introduces a completely new system for the regulation of distributions by a company to its shareholders. The preferred method for protecting the interests of creditors in distributions is now based on a solvency and liquidity test. Regrettably, the provisions setting out the requirements for distributions on the one hand and the solvency and liquidity test on the other have been poorly drafted. This thesis first explains and then applies an innovative interpretation theory to these provisions with a view to piecing together coherent content. The thesis finds that creative interpretations will not suffice in various places, meaning that substantive revision is required. The thesis concludes with brief amendment proposals and accompanying commentary.
URI: http://hdl.handle.net/10019.1/97133
Keywords: Business enterprises; Companies; Companies Act; 2008; Companies régulations; Company insolvency; Company liquidity; Insolvency; Régulations; Shareholders; South Africa

The effectiveness of the e-commerce legal framework in selected African countries - Esanwa, Maryam Adetokunbo (University of KwaZulu-Natal, 2015)
Abstract not available.
Keywords: Africa; E-commerce; Electronic commerce; Information technology

A critical appraisal of the misapplications of black economic empowerment and the common misperceptions that surround it - Govender, Prenisha (University of KwaZulu-Natal, 2015)
Broad-Based Black Economic Empowerment is a regulatory framework, which is unique to South Africa. This dissertation reflects upon the evolution of Broad-Based Black Economic Empowerment programme, from the commencement of apartheid to date. Broad-Based Black Economic Empowerment was implemented by government, with the objective of resolving the injustices created by the apartheid regime. Government seeks to achieve this objective by integrating the historically disadvantaged individuals within South Africa into the mainstream of the economy. However, the reality is that the implementation of the Black Economic Empowerment programme has not been entirely successful. This dissertation is a critical analysis of the application of Broad-Based Black Economic Empowerment and related legislation. It aims to highlight the challenges faced by government in enforcing the Broad-Based Black Economic Empowerment programme, with a particular focus on the following issues: fronting, misrepresentations and common misperceptions. This dissertation begins by reflecting upon the historical context of South Africa toward democratization, secondly it analyses the current applicable legislation and explores the current issues. This research shows that Broad-Based Black Economic Empowerment is essentially a work in progress programme as there is much room for improvement. Scholars have established that companies and other entities regularly circumvent the Act. Furthermore, many individuals misunderstand the programme and its purpose. The research concludes Broad-Based Black Economic Empowerment does have potential for success. In considering the approach taken by Malaysia, it is established that the key to overcome these major issues is education.
Keywords: Affirmative action programs; Blacks Economic conditions; Business enterprises; Employee empowerment

Harmonising investment laws in the OHADA space - Mugangu, Marie Providence Ntagulwa (University of Cape Town, 2015)
The Organisation for the Harmonisation of Business Law in Africa (OHADA) was established for the purpose of restoring legal and judicial security in the region to attract more investment. The OHADA Treaty included certain areas of business law within its ambit but omitted investment law. There are several laws on investment in the region at the national, regional and sub-regional level that regulate the treatment of foreign investments such as CEMAC and UEMOA investment charters. Moreover OHADA states sign BITs to protect foreign investments. The relationship between the different sub regional laws on investment and OHADA is not yet clear but case law suggests that CEMAC and UEMOA courts recognise the supremacy of OHADA law and their lack of competence to hear matters regulated under OHADA. The standards of protection granted by OHADA states in BITs are very high thus taxing on them. This thesis suggests that OHADA states should either qualify these standards of protection or replace them with more specific provisions. The OHADA system of arbitration cannot effectively settle investment disputes arising out of a BIT leaving international arbitration systems such as ICSID as the best alternative to resolve investment disputes arising out of BITs.
Keywords: International Trade; International Trade Law; Investments

Avoidance of a contract under the CISG - Otenga, Emongo Jean-Marc (University of Johannesburg, 2015)
Keywords: CISG; Commercial law; Contracts (International law); United Nations Convention on Contracts for the International Sale of Goods (1980 April 11)

A comment on debt relief options for insolvent consumer debtors in South Africa - Xulu, Anele Innocentia Nombuso (University of KwaZulu-Natal, 2015)
The paper will be focused on examining the debt relief options available for consumer debtors in South Africa. This paper will look at the relationship between the National Credit Act 34 of 2005 and the Insolvency Act 24 of 1936. Further, it will examine the relationship between the provisions of section 74 of the Magistrates’ Courts Act 32 of 1944. The paper will conclude by looking at debt relief options available for consumer debtors in the United States of America and in England and Wales and will make comparative comments and recommendations on how we can adopt some provisions into our own insolvency system.
Keywords: Consumer credit; Debt relief; Debtor and creditor; Insolvency; Insolvency Act; National Credit Act; South Africa

The transfer of movables in the international commercial context – a comparison of German and South African law - Lengyel, Martin (University of Johannesburg, 2014)
L.LM. (International Commercial Law) Please refer to full text to view abstract
Keywords: Contracts (International law); Germany; International Commercial Law; Law of property; Property; South Africa

Proposal for a regulation on a common European sales law - Ciceri, Eliane (LUISS Guido Carli, 2014)
Historical development. Five W of CESL. Common European sales law.

The strategic importance of regional economic integration to multinational companies (MNCs) : a study of South African MNCs' operations in the SADC - Egu, Mathew Eleojo (University of South Africa, 2014)
Though the strategic importance of regional economic integration to multinational companies (MNC) has been researched extensively internationally, this concept has not been studied in South Africa. In fact, there is a growing nostalgia that with the South African Development Community (SADC) moving towards its set macroeconomic convergence targets; regional economic integration eventually leads to macroeconomic stabilisation. This ultimately becomes the root of growth in a region that has been severely affected by globalisation, financial crises, increasing government debt and budget deficit problems. This study, hence, tries to find out how the critical decisions of South African MNCs are made when operating within regional markets. Consequently, statistical econometric models were developed to test time-series data from 1980-2011 using the best (most efficient) linear unbiased estimator (BLUE) ordinary least square regression technique. An analysis was then done to investigate how South African firms have been able to gain maximum benefits by adopting the SADC as its major trading bloc in Africa. The study’s findings showed that the major barriers that impede MNCs of South African origin from penetrating these markets were custom duties, direct and indirect tariffs. It was observed that this would only be reduced by regional integration. Determined to critically interrogate the problems detailed in this research, three hypotheses were tested, analysed and subsequent interpretation of the findings revealed that South African MNCs contribute positively to regional economic growth and investment in the SADC. Furthermore, the study found out that although these factors were important, they were not the only variables that stimulated the competitiveness of South African MNCs in the SADC region. The literature review sections of this study found that the adoption of strategic management initiatives by MNCs improved the operation of transnational companies in South Africa. A comparison between the value of South African MNCs, as well as, other explanatory variables, and the Gross Domestic Product (GDP) of both South Africa and the SADC using time series data for the period 1980-2011 indicated that there was a positive relationship between the contribution of MNCs to South Africa’s economy and the GDP of both South Africa and the SADC. This proved that there is a significant link between MNC growth and national/regional productivity. In conclusion, the study established that the findings of the literature review were theoretically in sync with the empirical analysis. Also, the outcome of this study concurred with the findings of similar research. In essence, regional trade arrangements are an increasingly important element of the global trade environment, of which the move by South Africa’s MNCs to operate in the SADC market was a positive one. Finally, the study found out that for these firms to be successful in the international business arena, business management decisions need to be made, only after a detailed strategic analysis of the significance of regional economic integration is considered. This integrative framework certainly determines the operational efficiency, survival and profitability of most MNCs that operate within the region.
Accepted: 2014-10-01T07:01:54Z
Keywords: FDI; Foreign direct investment; Macroeconomic convergence; Macroeconomic stability; Mergers & acquisitions; Multinational companies; Regional Economic Community; Regional Trade Agreements (RTAs); SADC; South Africa Development Community; Strategic management

The compatibility of Australian and South African private international law with the Hague Principles on Choice of Law in International Commercial Contracts - Adams, Faadhil (University of Johannesburg, 2014)
In 2006 the governing body of the Hague Conference on Private International Law furnished the Secretariat with a mandate to conduct a series of feasibility studies on the development of an instrument, relating to the choice of law in international contracts. The outcome of these studies was largely successful, finding that there was a need for an instrument of this nature and additionally it would be welcomed by the international legal community. In 2009 the Permanent Bureau of the Hague Conference on Private International Law was invited to form a Working Group (WG) to draft a soft-law instrument affirming party autonomy in international contracts on an international level. The Hague Principles on Choice of Law in International Commercial Contracts (P) was, thus, born. The P were drafted by a panel of experts representing the majority of the world’s legal systems. The working group commentary (WGC will be used to refer to the commentary, whilst WG will be used to refer to refer to the working group itself) which provided the discussions in respect of, and the reasoning behind, the principles has been invaluable in writing this dissertation. The purpose of this dissertation is to investigate the compatibility of Australian and South African law with the P. One of the aims of the P mentioned specifically in the preamble is that these principles are to be used by countries as a model with which to develop their own rules of private international law. A study of the current law as it stands in comparison to the P marks the first step in this exercise, through finding where the law differs we can begin to bridge the disparity between a specific country’s legal system and that of the P. Should the P become an important part of the private international law discourse comparative studies such as this will become common-place. The fact that the principles were drafted as a soft-law instrument is in line with the growing world trend. The flexibility that is achieved through the use of a soft-law instrument may lead to greater legal certainty down the road as contracting parties and international lawyers alike become more familiar with the principles. This familiarity may lead to consensus among experts from around the world and eventually invite the prospect of a binding instrument being drafted
Keywords: Australia; Conflict of laws; Contracts; Contracts (International law); South Africa

Addressing the legal issues of an innovative start-up company - Samoylov, Vlad (Victoria University of Wellington, 2014)
Before examining the substance of the law it is necessary to discuss the contrast between law and practice. It is important to keep in mind that the letter of the law is sometimes not what is done in practice. This realisation is often referred to as the “law and society perspective.” Advocates of this perspective treat legal doctrine as more than just a closed system because they recognise that there are other external influences at play. Beyond the law, people are also influenced by other factors such as social roles, morals, religion and culture. For example, university researchers have an external incentive mechanism outside of IP law. Such researchers frequently prefer to publish their results and discoveries in academic journals rather than file for patents. A patent cannot be granted where there has been a publication. However the researchers are motivated by other incentives such as access to research funds and the attainment of professorship. The Law and Society perspective highlights the fact that the formal processes, which are provided for by the law are at times substituted by informal customs and understandings. An information technology (IT) firm that contributed to this paper by participating in an interview (Interviewee A), provided a good example of such an occurrence. Rather than use any of the formal IP modes of protection which are discussed in the following sections of this paper, ‘Interviewee A’ uses a very unorthodox strategy to protect their IP. They said: “we rely on employment contracts, code of conduct, and especially personal ethics and behaviour to protect our IP. We therefore have a company culture that encourages teamwork and cooperation”.
Keywords: Intellectual property; Product safety standards

Mediation advocacy - Shaw, Annabel (Victoria University of Wellington, 2014)
Mediation has been a part of New Zealand’s employment statutory framework in one form or another for over a century, and has been the first port of call for employment disputes under the current Employment Relations Act for nearly 15 years.¹ I have been working as a mediator in this context for almost seven years in more than 1,000 mediations. Lawyers are playing a significant part in the field of mediation, with a large number representing clients in this forum on a regular basis. In an evaluation of 100 of my mediations over a ten-month period, 85% of parties were legally represented. This rate is consistent with anecdotal reporting across the employment mediation service. Lawyer representation in mediation is not unique to the employment context. There are various mediation schemes provided for under many New Zealand statutes as well as a wide raft of non-statutory mediation occurring in numerous settings. In my experience as a mediator with human rights and leaky building mediations, as well as working as a lawyer in a large commercial law firm, I am aware lawyers are representing clients in many other areas of mediation as well. Although there is a significant amount of mediation occurring and a large number of lawyers regularly appearing in mediation, my experience is that the majority of lawyers act in mediation as if they were in litigation and take an adversarial approach. My thesis is that lawyers have not adapted effectively to mediation and taken on the role of mediation advocacy. This paper explores the topic by first describing, in Part II, what I observe as lawyers’ adversarial approach in mediation. It then looks at other research to assess whether this experience is reflective of a wider issue. It finds there is evidence to support my observations. Part III analyses why lawyers are operating in an adversarial way in mediation and proposes several reasons this may be the case. Part IV puts forward what I propose is appropriate mediation advocacy. It sets out the knowledge, roles and skills required from lawyers when representing clients in mediation. Part V suggests what might be done to assist a shift away from the common, adversarial approach to effective mediation advocacy. This paper is written within the context of employment mediation in New Zealand. However, it draws on research from different jurisdictions and areas of practice so the conclusions it comes to may have more general application. The topic is not whether lawyers should be in mediation. I am not arguing that lawyers do not have a part to play in mediation. A lawyer well versed in mediation advocacy can play a highly effective part in the process. Leonard Riskin, one of the key authors on the topic of lawyers in mediation, expresses this even more strongly, saying he believes lawyers’ involvement is fundamental to mediation’s success.² Further, this paper is focused on lawyers representing parties in mediation and does not consider lawyers as mediators.
Keywords: Advocacy; Dispute resolution; Employment disputes; Lawyers; Mediation

Sanitary and phytosanitary measures in the SADC region : a South African legal perspective - Joubert, Biandri (North-West University, 2014)
Sanitary and phytosanitary (SPS) measures are measures aimed at the protection of human, animal and plant life and health within specified territories from the risks associated with the introduction and spread of pests and diseases through trade. The World Trade Organisation (WTO) developed an agreement on the application of SPS measures. South Africa is a member of both the WTO and the Southern African Development Community (SADC). In SADC, SPS measures are provided for in the SADC Sanitary and Phytosanitary Annexure to the Protocol on Trade of 1996. International Standard Setting Bodies (ISSBs) facilitate the effective application of the main elements of the relevant SPS agreements, especially harmonization and equivalence by establishing scientifically justified standards on which members may base their SPS measures. The relevant ISSB’s in terms of SPS measures are the OIE, IPPC and Codex Alimentarius. SPS measures have the potential to become or be used as non-tariff barriers to trade (NTBs). The SADC Protocol on Trade 1996 stipulates that policies and measures are to be implemented by members to eliminate existing forms of NTBs. Additionally members may not enforce new NTBs affecting or related to intra-SADC trade. The most relevant South African legislation in the context of SPS measures and this study is as follows: Agricultural Pests Act 36 of 1983, the Agricultural Products Act 119 of 1990; the Fertilizers, Farm Feeds, Agricultural Remedies and Stock Remedies Act 36 of 1947, the Liquor Products Act 60 of 1989, Meat Safety Act 40 of 2000, Foodstuffs, Cosmetics and Disinfectants Act 54 of 1972, Medicines and Related Substances Act 101 of 1965 and National Regulator for Compulsory Specifications Act 5 of 2008. The purpose of this study is to establish to what extent the South African legal framework complies with its obligations in terms of the SADC SPS Annexure to the Protocol on Trade.
Keywords: ISSB; NTB; SADC; SPS; Sanitary and phytosanitary measures; South Africa; WTO

A critical assessment of the impact of SPS measures on market access for developing countries : case study of South Africa and Kenya - Mupure, Ngonidzashe L. A. (University of KwaZulu-Natal, 2014)
Abstract not available.
Keywords: Developing countries; Economic conditions; Economic development; International Trade; Kenya; Phytosanitation; South Africa

A critical discussion on foreign direct investment in the multilateral trade system and development in SADC - Nhlakanipho, Macmillan Zikalala (University of KwaZulu-Natal, 2014)
Development is understood to be an economic process that aims at a constant improvement of the well-being of all individuals who have the right to participate and benefits from the fruits of development. Development is also a right that requires a progressive realisation by governments, international communities and private sectors to the satisfaction of all individuals. A progressive realisation of this right requires a vibrant economy, which can be acquired through International trade and Foreign Direct Investment (FDI). It is in this context that this thesis has attempted to discuss the influence of FDI and International trade on development. The discussion was initiated by focusing on the history of the multilateral trade system (MTS) by looking at various Ministerial rounds of both the General Agreement on Tariffs and Trade (GATT) and the World Trade Organisation (WTO). In this discussion the thesis found that, whilst there are various multilateral political frameworks regulating trade, FDI is subject to regional and domestic political frameworks. The thesis also discussed development in relation to the millennium development goals (MGDs). It was established the goal eight of the MDGs requires the integration of poor countries into the MTS so that they can be able to exploit their comparative advantage. This goal influenced the launching of the Doha Development Agenda (DDA) at the Doha round in 2001. However, the thesis also established that conclusion of the DDA has been progressing at a slow pace. Therefore it has not yielded substantial results for poor countries. The failure to conclude the DDA has led to an increase of Regional Trade Agreements (RTAs), which some scholars view as a supplement of multilateral trade integration. However, the SADC region has not been able to conclude their integration objectives due to the fact that many member states belong to other RTAs. In the case of FDI the thesis established that FDI is accompanied by a wide range of resources for host countries, which can be utilised for enhancing development. However, it was also established that the SADC has not been able to attract lucrative FDI due to a wide range of factors that impede FDI. On this finding, a case study was employed on four countries in the region, namely Angola, Botswana, South Africa and Zimbabwe.
Keywords: Economic Policy; FDI; Foreign direct investment; International Trade; International economic relations; Investments

Copyright and developing countries a critical examination of recent developments in copyright law with particular reference to the impact on developing countries and access to educational materials - Siphepho, Nomvuyo Nicole (University of KwaZulu-Natal, 2014)
Abstract not available.
Keywords: Copying processes; Copyright; Developing countries; Instructional materials industry

Corporate governance in Kenya's state corporations: A critique on the appointment and dismissal of directors of boards of state corporations - Kamau, A. G. N. (University of Nairobi, 2013)
This study interrogates corporate governance practices within Kenya’s State Corporations with particular reference to the appointment and dismissal of directors of the Boards of these corporations. It recognizes that these directors are the anchors for the implementation of corporate governance practices in these corporations. The appointment and dismissal of these directors have been based on, inter alia, political considerations kinship, patronage, ethnicity and other non objective criteria other than merit. This has often impacted negatively on the performance of these corporations. This study traces the evolution of corporate governance generally, documents it’s historical development in Kenya and examines the current practices on the appointment and dismissal of directors of boards of state corporations. The data collected targeted a majority of State Corporations which demonstrates that past criteria for Directors recruitment and their dismissal was based on non objective criteria. The study is instructive on the fact that though best practice and corporate governance principles have not been fully embraced in the appointment and dismissal of Directors of Boards of State Corporations there is a positive move towards the adoption of these principles in such appointments and dismissals. The impetus for this was the promulgation of the Kenya constitution 2010 which is itself a good corporate governance document.

Business income and passive income in the UN model double taxation convention - Mascia, Susanna (LUISS Guido Carli, 2013)
The historical evolution of the UN model convention. The UN model convention’s subjective and objective scope. The determination of active income: current points of difference between the UN and OECD models. The determination of passive income: differences and similarities between the UN and the OECD model conventions. Transfer pricing.

Unlocking Africa's poverty trap : holistic approach to BOP investment in agribusiness - Suzuki, Elli (Massachusetts Institute of Technology, 2013)
This paper identifies subsistence farming as a significant opportunity for poverty reduction and economic development in sub-Saharan Africa. By taking a holistic, standardized, and bundled approach, this paper proposes an innovative business model that enables small-holder farmers to access affordable extension services, technical assistance and financial scheme, thereby improving their overall productivity level.

A Comparative study of some issues relating to Corporate Insolvency Law in Nigeria and South Africa - Habi, Halita Mafo (University of Pretoria, 2013)
No abstract available

Users' entitlements under the fair dealing exceptions to copyright - Shay, Richard Michael (Stellenbosch University, 2012)
This thesis analyses current South African copyright law to ascertain the proper interpretation and application of the fair dealing provisions contained in the Copyright Act 98 of 1978. Copyright law ensures that authors’ works are not used without their consent, which they can grant subject to compensation or conditions attached to the use. Fair dealing exceptions allow the general public to use copyright works for certain purposes without the copyright owner’s consent and without paying compensation. These provisions are intended to balance copyright owners’ interests with the interest that members of the public have in using copyright works for socially beneficial purposes. These provisions typically allow the use of a copyright work for the purposes of research or private study, personal or private use, criticism and review, and news reporting. Unfortunately there is no South African case law concerning the fair dealing provisions, and the application of these exceptions remains unclear. This study aims to clarify the extent of application of the fair dealing exceptions to copyright infringement so that courts may be more willing to consider foreign and international law and in doing so develop South African intellectual property law. The social and economic policy considerations underlying the fair dealing exceptions are considered to determine their function. International conventions relating to copyright and neighbouring rights are examined, specifically the provisions allowing exceptions to copyright. The legislation and case law of Australia and the United Kingdom are analysed to determine the proper interpretation and application of these statutory defences. This knowledge is then used to inform South African law. The Copyright Act 98 of 1978 does not contain a fair dealing exception for parody and satire. Australian legislation does contain such an exception, and it is analysed in that context. An exception for parody is proposed for South African law, and the need for and application of this provision is considered. The constitutionality of the proposed exception is evaluated in terms of its impact on the constitutional property rights of copyright owners.
Keywords: Australia; Copyright law; Fair dealing; Fair use; Great Britain; Intellectual property; South Africa; Trademarks

The Influence of ICC Arbitral Decisions on Canadian Law: Comparative Study between Civil Law and Common Law Jurisdictions - Hedaraly, Saleha (Université de Montréal, 2012)
L’objectif de cette recherche est de démontrer que les décisions arbitrales de la Chambre de commerce internationale peuvent être considérées comme une source potentielle de droit au Canada. Il existe actuellement une incertitude quant au droit matériel utilisé en arbitrage international pour résoudre les différends commerciaux. Bien que l’utilisation de la lex mercatoria pour résoudre un litige soit une option, elle se heurte à de nombreuses incertitudes terminologiques et conceptuelles. L’utilisation d’une approche méthodologique de la lex mercatoria permettrait une classification de ses sources en deux branches: (1) le droit statutaire international et (2) le stare decisis des tribunaux d’arbitrage commercial international. Une telle approche méthodologique conférerait plus de certitude quant à l’application d’un droit uniforme. De plus, elle faciliterait l’étude de l’interlégalité entre les règles de la lex mercatoria et le droit matériel interne. Plus particulièrement, elle permet de comparer les similitudes et les différences des règles du droit matériel entre les décisions arbitrales internationales, le droit statutaire international et les juridictions canadiennes de common law et de droit civil. Cette comparaison rend possible une évaluation de l’influence potentielle des décisions arbitrales de la Chambre de commerce internationale sur le droit matériel canadien et si cette influence est plus importante en droit civil ou en common law. This paper’s objective is to demonstrate that the International Chamber of Commerce’s arbitral awards may be considered as a potential source of law in Canada. There currently exists an uncertainty as to the substantive law used in international commercial arbitration. While the use of lex mercatoria to solve commercial disputes is often referred to, several terminological and conceptual uncertainties undermine its credibility. The use of a methodological approach to lex mercatoria allows for a twofold classification of its sources through: (1) international legislation and (2) stare decisis from international arbitral tribunals. This methodological approach provides a greater certainty for the application of a uniform law which, in turn, allows for the study of interlegality between rules of lex mercatoria and substantive domestic law. Furthermore, this methodological approach facilitates the demonstration of the similarities and differences between international arbitral decisions, international legislation as well as Canadian common law and civil law jurisdictions. This comparative analysis will allow the study of the potential influence of the arbitral decisions of the International Chamber of Commerce on substantive Canadian law and whether this influence is more important in civil law or common law.
https://papyrus.bib.umontreal.ca/xmlui/bitstream/handle/1866/12719/Hedaraly_Saleha_2012_memoire.pdf
Keywords: Approche méthodologique; Arbitrage; Arbitragem; Arbitral decisions; Arbitration; CCI; Civil law; Common law; Droit civil; Droit commercial transnational; Décisions arbitrales; ICC; Interlegality; Interlégalité; Lex mercatoria; Methodological approach; Sentences arbitrales; Transnational commercial law

A regulatory framework for the trans–boundary transportation of dangerous goods in Southern Africa : an environmental perspective - Ashukem, Jean-Claude Nkwanyuo (North-West University, 2012)
The goal of this dissertation is to analyse the extent to which the South African legal framework governing the trans-boundary transportation of dangerous goods, provides for the regulation of environmental aspects in terms of dangerous goods transportation. The dissertation examines the role of regional and sub-regional laws in this regard in an effort to ascertain whether there is sufficient legal certainty and harmonisation of laws for environmental regulation. No specific law currently exists in South Africa regarding the regulation of dangerous goods transportation, rather the regulation of dangerous goods is effected by a multiplicity of laws. This state of affairs illustrates the difficulty that exists and may be associated with the enforcement of the regulation of dangerous goods transportation. Despite this, the multiple laws vividly elucidate the fact that there is a considerable degree of environmental protection vis-a-vis dangerous goods transportation premised on the fact that all environmental impacts could never be avoided or eliminated, but can be reduced to an extent.

Combating insider trading in Kenya's capital markets: challenges and opportunities for reform - Kotonya, Anne (University of Nairobi, 2012)
The capital markets are expected to play a pivotal role in the attainment of Kenya's development blueprint 'vision 2030.' It is, therefore, essential that obstacles to the attainment of a fair and efficient market are examined and rooted out. This study investigates the limitations of the Capital Markets Act in combating insider trading. It also examines whether reforms would promote a fair and efficient capital market. The study makes use of existing literature as well as decided cases to investigate the inadequacies in the formulation of and provisions for inside information, material pricesensitive information, publication of information, possession of information and disclosure of information in the Capital Markets Act. This literature draws out key learnings from other jurisdictions and analyses how legislation in developed economies treats challenges to the enforcement of insider trading laws. The doctrinal analysis is triangulated with results of a survey of practical experiences of legal practitioners in applying the Capital Markets Act. The findings affirm the existence of conceptual difficulties in determining the elements of the crime of insider trading. As a consequence, it is concluded that the present formulation of insider trading law is inadequate. The study, therefore, makes suggestions for reforms to the provisions on insider trading in the Capital Markets Act.

Challenges to regional intergration in the SADC region : a legal perspective - Mwanawina, Ilyayambwa (North-West University, 2011)
The Southern African Development Community (SADC), formerly known as the Southern African Development Coordination Conference (SADCC), is an organization of Southern African states initially formed to reduce economic dependence on South Africa (then an Apartheid state) and to harmonize and coordinate development in the region. The vision and mission of SADC reach well beyond the harmonization of development within the region. It extends to fields that include political stability, peace building, the maintenance of security and justice as well as economic cooperation. The attainment of these goals requires well co-ordinated regional mechanisms; as such over the past decade member states have paid particular attention to the possibility of attaining these goals through regional integration. The transformation from SADCC to SADC indicated that the body would no longer be a loose association (conference) of states but rather a regional body that would have a legally binding effect on its member states. The question is, when the member states assembled in Windhoek, August 1992, did they create an institutional framework, and policies that would have enough legal force to ensure that the institutional agenda of integration is not defeated by member states? The argument of this dissertation is that the Treaty and the policies established afterwards contain principle imperfections that are self defeating for the pursuance of regional integration. The work will begin by discussing regional integration in general, highlighting the historical origins of SADC as well as the role of the African Union. The work will then discuss the dimensions and functioning of SADC, laying the foundation for a proper critique on how the institutional framework contains inherent weaknesses that eventually hinder the progression of SADC. The dissertation ultimately will discuss and benchmark the European Union against SADC, in an attempt to extract important lessons for the progression of SADC.
Accepted: 2016-01-10T22:52:56Z https://repository.nwu.ac.za/handle/10394/15788
Keywords: Africa; Interregionalism; Southern

International convention for the control and management of ships' ballast water and sediments, 2004 - Robe Hughes, Charlotte (Aix-Marseille Université, 2011)
Will harmonization of legislation relating to the management of ships’ ballast water be achieved, once IMOs’ 2004 Convention enters into force?

Legal origins, legal institutions and poverty in Sub-Saharan Africa - Baldelli, Federico (LUISS Guido Carli, 2010)
The traditional and religious layer. The colonial layer. Law of independence. Law in Sub-Saharan Africa today. Common law and civil law in Sub-Saharan Africa. The consequences of legal origins. Legal origins and legal institutions in Sub-Saharan Africa. Legal origins and poverty in Sub-Saharan Africa. An econometric model.

The implications of the structure of the regulatory expropriation enquiry in international investment law - Bonnitcha, Jonathan Merrington (Oxford University, UK, 2008)
This thesis examines the structure of enquiry that arbitral tribunals use to distinguish between regulatory expropriation and legitimate non-compensable regulation in international investment law. The thesis proposes a new taxonomy of the possible structures of enquiry: the enquiry could look exclusively to the effects of the measure on the protected property; exclusively to the characteristics of the impugned measure; or to both the effects on the property and the characteristics of the measure. The application of this taxonomy shows that there is no agreed structure of enquiry in decisions on regulatory expropriation in international investment law. However, various threads of jurisprudence do show some degree of internal consistency. The thesis identifies six approaches in the decisions of arbitral tribunals: two that look exclusively to the effects of the measure; one that looks exclusively to the characteristics of the measure; and three that consider both the effects and the characteristics of the measure. Of the three approaches that consider both the effects and the characteristics of a measure, one is a direct adoption of US 5th Amendment jurisprudence and another is a direct adoption of ECHR Article 1 – Protocol 1 jurisprudence. Chapters 4 and 5 examine the jurisprudence of the US and ECHR in detail. These chapters show that, unlike international investment law, each of these jurisdictions has an established structure of enquiry in cases of regulatory expropriation. All six approaches to regulatory expropriation are sketched as models. These model approaches are applied to the case study of Piero Foresti. The case study demonstrates the most significant conclusion of this thesis: that different structures of enquiry, and different approaches within those structures, necessarily entail different legal outcomes on the same facts.
Keywords: 5th amendment; Bilateral Investment Treaties (BITs); Black economic empowerment; ECHR; Expropriation; Human rights; International Investment Law; MPRDA; Property law; Public international law; Regulatory expropriation; Right to property

Explaining Copyright: The Normative Implications of its Sociotechnical Construction - Nicholson, Scott (Queen’s University, 2008)
The construction of copyright law can be causally explained by two possible types of explanation: dialectical explanations and material explanations. I argue that an adequate causal description of the copyright discourses of Western legal systems must incorporate a material explanation in order to account for many of the general and particular characteristics of the evolution of copyright. As a vast variety of contingent and interactive social and technical conditions have caused the evolution of copyright, we should expect a plausible material explanation to be multifaceted and multi-layered. However, in addition to providing a causal sociohistorical description, a good legal explanation should also seek to include a normative account detailing the moral grounds of the law, or lack thereof. Dialectical explanations can be teleological: they can presuppose that the law is directed towards a perfect legal state and that it is essentially guided by a set of moral ideals. Material explanations, on the other hand, are essentially non-normative and do not explicitly address moral questions. But this does not entail the elimination of moral considerations from material explanations. As I aim to show, we should not address the moral and sociohistorical elements of copyright legal discourses independently because they are causally connected: moral justifications have been rhetorically used by social actors to influence lawmaking processes, and conversely, changes in technical conditions have given rise to sociotechnical formations that enable and structure the norms of copyright. Given this, I propose that lawmakers should adjudicate and legislate from a broad and flexible standpoint. They should not attempt to merely apply old principles to new problems, but should comprehend new moral norms introduced by new conditions, and balance them against the older, more established principles enshrined in traditional intellectual property theories.
QSpace: Queen's Scholarship & Digital Collections
Keywords: Copyright; Intellectual property

Small economies and their development in the Multilateral Trade System: correlation between economic and political environment and trade performance of small economies - Tiemeni, Thierry Galani (University of the Western Cape, 2007)
At the heart of this study is the topic of small economies in the Multilateral Trade System (MTS). The study examines the World Trade Organisation’s (WTO) legal framework and policy objectives in order to develop a comprehensive definition of small economies as a group of WTO members with specific needs. Particular attention is given to the determination of the specific characteristics of small economies, as well as the issues and constraints they are facing in the MTS. The study explores solutions proposed in order to tackle the constraints to the effective integration of small economies in the MTS, with specific reference to the policy reasoning of small economies. More importantly, the study explores the impact of the size factor, which is certainly not only a burden on the growth and development perspectives of the considered entity, but which may also become an advantage and promotes the trade performance of a small economy. Hypotheses are then made relating to the relevance of the economic and political environments in the determination of a successful (or not) integration, and participation, of a small economy in the MTS. A crucial argument developed is that the differences observed between countries sharing similar characteristics of smallness, vulnerability and remoteness/landlockedness, illustrates the fact that what ultimately matters is the interplay of factors related to the economic and political environments, the effect of which is to promote or constrain (depending on the case) successful integration of the small economy in the MTS.
https://hdl.handle.net/10566/18256
Keywords: Committee on trade and development; Developed countries; Economic environment; Multilateral trade system; Political environment; Small and vulnerable economy; Small economies; Trade performance; WTO; World Trade Organization

The legal risks associated with trading in derivatives in a merchant bank - Terblanché, Janet René (University of Stellenbosch, 2006)
The research defines derivatives as private contracts, with future rights and obligations imposed on all parties, used to hedge or transfer risk, which derives value from an underlying asset price or index, which asset price or index may take on various forms. The nature of derivatives is that the instruments are intended to be risk management tools. The objectives of derivatives are either to hedge a risk, or to speculate. Derivatives may be classified by the manner in which they are traded, either over the counter (OTC) or on exchange. Alternatively, derivatives may be classified on the basis of structure and mechanisms, i.e. forwards, futures, options or swaps. Risk and risk management are defined in the third chapter with the focus on merchant banking. The nature of risk is that it is inherent in all activities. The nature of risk management is that it aims to ensure that the risks faced by the merchant bank are managed on a daily basis. The objective of risk management is to ensure that losses are minimised and the appropriate level of risk is taken in order to maximise profits. Risk may be classified as operational, operations, market, systemic, credit and legal risk. A comprehensive discussion of credit risk is presented, as it pertains to the legal risk in derivatives in a merchant bank. This includes insolvency, set-off, netting, credit derivatives and collateral. Legal risk is defined as the risk of loss primarily caused by legal unenforceability (i.e. a defective transaction, for instance a contract), legal liability (i.e. a claim) or failure to take legal steps to protect assets (e.g. intellectual property). The nature of legal risk is that it is caused by jurisdictional and other cross-border factors, inadequate documentation, the behaviour of financial institutions, a lack of internal controls, financial innovation or the inherent uncertainty of the law. The objectives of legal risk management in derivatives are to avoid the direct and indirect costs associated with legal risk materialising. This includes reputational damage. Derivatives attract specific legal risks due to the complexity of the instruments as well as the constant innovation in the market. There remains some legal uncertainty regarding derivatives in terms of gaming, wagering and gambling, as well as insurance. The relationship between risk and derivatives is that due to the complexity and constant innovation associated with derivatives, there are some inherent risks to trading in derivatives. It is therefore important to ensure that there is a vested risk management culture in the derivatives trading environment. Chapter four gives an overview of derivatives legislation in foreign jurisdictions and in South Africa. The contractual and documentation issues are discussed with reference to ad hoc agreements, master agreements and ISDA agreements. The practical implementation issues of master agreements and ad hoc agreements are also discussed. The recommendations are that legal risk management be approached in a similar manner to credit, market and other risk disciplines. A legal risk management policy needs to be developed and implemented. The second recommendation is that a derivative to manage the legal risk in derivatives be developed.

The role of implicit contract terms as a determinant of contractual consequences - Bailly, Chantal (Stellenbosch University, 2005)
Banks are one of the most important elements in the economic cycle of modem society. As money replaced bartering banks have gradually moved into the pivotal point of the relations between participants in the economic cycle. No project can be realized without money today. On the one hand, there are the investors who, irrespective of the amount, entrust their assets to the banks. On the other hand, there are those whose financial needs require the granting of some form of credit. Banks operating in these contexts clearly bear important responsibilities towards the different parties. A third party, the state, is also interested in a well-functioning banking establishment. Economic stability, without which there can be no political stability, cannot otherwise be ensured. The state is accordingly keenly interested in maintaining the operability of this system. To this end, various laws are made in the respective countries aimed at supervising the banking industry. This work deals with some of the legislation relating to bank supervision in the Federal Republic of Germany and the Republic of South Africa. In the various chapters certain aspects of bank supervision in the two countries are identified, juxtaposed and compared. The reasons for any differences are sought, discussed and where possible explained. From a historical point of view, the two countries developed differently. Nevertheless, the need to regulate this sector through legislative means arose at an early stage in both. Unfortunately, the catalyst for legislative development was mostly some or other financial crisis. Any measures for supervising banks must, to be binding, be constitutional. In this regard much must still be done in South Africa due to the fact that the New Constitution has only been in force since 1996. Thus certain regulations stemming from the Banks Act 90 of 1994 need to be reconsidered in the light of the constitution. Bank supervisory activity is performed by a national institution in both countries. Germany avails itself of an independent authority. However, in South Africa it is one of the tasks of the central bank which has established a specific office for this purpose. Legal and natural persons alike are subject to such supervision. Diverse other government institutions provide support for such supervisory work in both countries. The scope of banking supervision, that is the persons and transactions affected, is broad and also finely meshed. Both systems list a number of banking transactions that are subject to their supervision. This affects all domestic banks and all foreign banks that are domestically active. Access to the banking business is only permitted in both countries after an appropriate license has been granted. The license can be conditional. Moreover, both systems make provision for the revocation of the license in appropriate circumstances. The conducting of banking business without the necessary permission is forbidden in both countries under the threat of legal punishment. It is well recognized in modem society that legal subjects should be protected against the decisions of those who wield state power. The possible remedies of those affected by the decisions of the public authorities responsible for banking supervision in the different countries are investigated in conclusion.
Keywords: Contracts; Good faith

The legal regulation of corporate governance with reference to international trends - Horn, Roelof Combrinck (University of Stellenbosch, 2005)
Corporate governance is defined as the system by which companies are managed and controlled. The concept came to the fore with the Cadbury Report in England in 1992 and has since been the topic of much academic discussion. The recent collapse of companies like Enron and WorldCom raised serious questions about international corporate governance practices. This has resulted in widespread reform. In the United States large-scale prescriptive measures were implemented through the enactment of the Sarbanes-Oxley Act. The United Kingdom persisted with their principle-based approach of comply or explain, although some amendments were made to the Combined Code through a joint effort by the Co-ordinating Group on Audit and Accounting Issues, the Smith Report and the Higgs Report. In Australia change took the form of the ASX Corporate Governance Principles and CLERP 9. South Africa, influenced by its common law background, followed a similar approach to that of the United Kingdom but has recently adopted a more prescriptive approach similar to that of the US. The King Committee was set up to review corporate governance in South Africa and two reports report were published – one in 1994 and another in 2002. Amendments to the JSE Listings Requirements followed. The Konar Report made recommendations on the reform of the accounting and auditing profession. The Department of Trade and Industry has recently launched a review of South African company law in conjunction with a review of the audit and accounting professions. These recent developments in company law will however not be discussed in depth as it is at a very early stage and is still subject to change. The aim of this study is to evaluate and determine whether or not the reform in South Africa is adequate to address the questions raised by recent corporate scandals in South Africa. The question also has to be asked whether South Africa should follow international trends in reform just for the sake of reforming. This requires an understanding of the principles underlying corporate governance and the reasons for the existence of corporate governance rules. With the increasing separation between ownership and control the accountability of directors has waned considerably. When addressing corporate governance issues, this must be kept in mind constantly. While the focus of recent reform has been on the company, its directors and auditors, the role of shareholders should not be ignored. What is needed to prevent directors and managers from abusing their positions of power are more informed and involved shareholders. The different role players must also cooperate in developing a culture of ethical behaviour and an environment of openness and accountability.

The powers of the Labour Court to review arbitration awards of the Commission for Conciliation, Mediation and Arbitration : a comparative study - Bezuidenhout, Susan Antoinette (University of South Africa, 2004)
A critical and in-depth discussion of the powers of the labour court to review arbitration awards of the Commission for Conciliation, Mediation and Arbitration, the application of the author's findings relating to common-law, legislation and case law and a critical analysis thereof. Special reference is made to the provisions of sections 145 and 158(1)(g) of the Labour Relations Act 66 of 1995 including, in particular, the alternative application thereof in practice and scope for improvement in order to address potential prejudice to parties occasioned by the compulsory nature of (certain) dispute resolutions. This thesis incorporates a comparative study of the British and German labour law systems with reference to the relevant appeal and/or review procedures (as applied in their tribunals/courts), together with a discussion and application of certain other provisions relevant to South Africa labour law.
Keywords: British Labour system; CCMA; Compulsory arbitration; Dispute resolution; German Labour system; Labour Court; Review procedure

An Appraisal of the Community Court of Justice of the Economic Community of West African States (ECOWAS) in Conflict Resolutions - Ibegbulam, Stellamaris (Ahmadu Bello University, 2001)
This thesis has found out that the court does not have an efficient means of coercion to apply delivered decisions, there by making the enforcement of the court’s decision cumbersome; decision of the court dealing with sanctions on member state who fail to fulfil their obligations are more complex than the interpretation of ECOWAS text; the research showed that the court also did not provide for the time limit in which an application can be reacted or responded to or time limit in which an annulment decision must be enforced. This thesis has put forth suggestions for the court. The suggestions essentially call for full subregional integration process by the court like all other ECOWAS institutions. The research revealed that the place of the court in the subregional integration will be more important if the decisions delivered by it can be enforced without encumbrance within the ECOWAS region; and that member states and some national institutions should not hold on tightly to their sovereignty but rather try to put enough zeal into facilitating rapid and efficient execution of decisions made by the court. This research work highlighted the extent of the powers of the Community Court of Justice and the factors that have led to it a judicial body with limited powers as regards the lack of access to court being by individual citizens, with the expansion of the provisions of the protocol, the court is bound to blossom in the scope of jurisdiction. It is hoped that this will help to move the sub-region towards greater integration so as to be able to compete in the new competitive global market. The ECOWAS Court has consistently demonstrated courage in the discharge of its vital role in putting an end to violation of all human rights and impunity of perpetrators in the sub region
Keywords: Conflict resolutions; Court of Justice; ECOWAS; West African States

The law relating to the supervision of banks : a comparison between the Federal Republic of Germany and the Republic of South Africa - Krammig, Andreas (Stellenbosch University, 1998)
ENGLISH SUMMARY: Banks are one of the most important elements in the economic cycle of modem society. As money replaced bartering banks have gradually moved into the pivotal point of the relations between participants in the economic cycle. No project can be realized without money today. On the one hand, there are the investors who, irrespective of the amount, entrust their assets to the banks. On the other hand, there are those whose financial needs require the granting of some form of credit. Banks operating in these contexts clearly bear important responsibilities towards the different parties. A third party, the state, is also interested in a well-functioning banking establishment. Economic stability, without which there can be no political stability, cannot otherwise be ensured. The state is accordingly keenly interested in maintaining the operability of this system. To this end, various laws are made in the respective countries aimed at supervising the banking industry. This work deals with some of the legislation relating to bank supervision in the Federal Republic of Germany and the Republic of South Africa. In the various chapters certain aspects of bank supervision in the two countries are identified, juxtaposed and compared. The reasons for any differences are sought, discussed and where possible explained. From a historical point of view, the two countries developed differently. Nevertheless, the need to regulate this sector through legislative means arose at an early stage in both. Unfortunately, the catalyst for legislative development was mostly some or other financial crisis. Any measures for supervising banks must, to be binding, be constitutional. In this regard much must still be done in South Africa due to the fact that the New Constitution has only been in force since 1996. Thus certain regulations stemming from the Banks Act 90 of 1994 need to be reconsidered in the light of the constitution. Bank supervisory activity is performed by a national institution in both countries. Germany avails itself of an independent authority. However, in South Africa it is one of the tasks of the central bank which has established a specific office for this purpose. Legal and natural persons alike are subject to such supervision. Diverse other government institutions provide support for such supervisory work in both countries. The scope of banking supervision, that is the persons and transactions affected, is broad and also finely meshed. Both systems list a number of banking transactions that are subject to their supervision. This affects all domestic banks and all foreign banks that are domestically active. Access to the banking business is only permitted in both countries after an appropriate license has been granted. The license can be conditional. Moreover, both systems make provision for the revocation of the license in appropriate circumstances. The conducting of banking business without the necessary permission is forbidden in both countries under the threat of legal punishment. It is well recognized in modem society that legal subjects should be protected against the decisions of those who wield state power. The possible remedies of those affected by the decisions of the public authorities responsible for banking supervision in the different countries are investigated in conclusion.
Keywords: Banks and Banking; Financial institutions; Germany; Government policy; South Africa

A Comparative Study of the Shipowner's Lien for Freight - Gazem, Abdelhamid (University of Glasgow, 1991)
The shipping business is an important element for the life of the trade of the different countries of the world. It had a very important role in the past it still has and it will always have, as it is the cheapest means of transportation of goods. However, despite the importance of this element the legal complexities bom out of this business makes it a broad subject of study and research for the lawyers. This is because of the different documents used for the execution of the contract of transport by sea and because of the speed these deals are concluded and the different nationalities of the parties to the contract.